Expression of wild-type and recombinant D4-CK domains of VWF gene with novel variants in Pakistan - Arshia Latif; Muhammad Asif Naveed; N. A. Shabana (Molecular Biology Reports, 2026)

Correction: Molecular characterization and cuticular stomatal anatomy of Punica Granatum L. cultivars study in Dohuk governorate - Dalal Y. Kh. Sinjare; Shamiran S. Abdulrahman; Nizek S. Khalid; Rizgar Y. Ismail; Muhammad Yasir Naeem; Zeliha Selamoglu; Gani Issayev; Aveen M. N. Ahmed (Molecular Biology Reports, 2026)

Core genome analysis reveals novel drug and vaccine targets in multidrug-resistant Citrobacter koseri - Zubda Ashraf; Fizza Arshad; Samina N. Shakeel; Faiz Ur Rahman; Khaled Fahmi Fawy; Sarah A. Altwaim; Saeed M. Alasmari; Abid Ali; Muhammad Umer Khan; Mohibullah Shah (Molecular Genetics and Genomics, 2026)

Stable isotopes and larger benthic foraminiferal response to the Paleocene-Eocene Thermal Maximum in the shallow-water carbonates of the Lower Indus Basin (Eastern Tethys, Pakistan) - Hafiz Shahid Hussain; April N. Abbott; Stefan C. Löhr; Muhammad Hanif; Sean T. Murray; Mohibullah Mohibullah; Mukhtiar Ghani (Journal of Asian Earth Sciences, 2026)

Techno-economic assessment of batch reverse osmosis desalination systems: Rating and design - Qais N. Al-Oweiti; Omar G. Kaoud; M.A.M. Ahmed; Faheem Ejaz; Muhammad H. Elbassoussi; Syed M. Zubair (Desalination, 2026)

Cellular and Microenvironmental Functions of SNHG lncRNAs in Tumor Immune Remodeling - Tareq Nayef Alramadneh; Afaq Mahdi Ali; Fatima Muhammad Yunus; Pareshkumar N. Patel; K. Jamuna; Vandana Tripathi; Priya Priyadarshini Nayak; Navin Kumar Tailor (Tissue and Cell, 2026)

Enhancement of photoelectrochemical water oxidation of surface-modified BiVO4/TiO2(001) via efficient cascade hole transfer - Munawar Khalil; Hafidatul Wahidah; Tribidasari A. Ivandini; Grandprix T.M. Kadja; Uji Pratomo; Muhammad N. Avicenna; Jacob Y. Mulyana; Fatwa F. Abdi; Andrivo Rusydi (Fuel, 2026)

Source-dependent effects of dietary astaxanthins on health and mucosal immunity in Atlantic salmon (Salmo salar) - S.M.Majharul Islam; Mette Sørensen; Gabriel Ossenkamp; Muhammad A.B. Siddik; Monica F. Brinchmann; Jørgen Lerfall; Viviane Verlhac-Trichet; Florence Perera Willora; Kim D. Thompson; Ioannis N. Vatsos (Fish & Shellfish Immunology, 2026)

Chalcogenophosphate CsMnPS₈ as a Promising Semiconductor for Photonic, Thermoelectric, Radiation-Protection and Energy Technologies - N. M.A. Hadia; Muhammad Irfan; Meshal Alzaid; M. F. Hasaneen; Abdullah Almohammedi (Journal of Fluorescence, 2026)

Not the same plastics: Comparing abundance and composition of marine macro-litter in mangroves and beaches in Southeast Asia - Jenny Fong; Ashwini Suresh Kumar; Cheng Ling Lim; Muhammad Reza Cordova; Pham T. Hoa; Deo Florence L. Onda; Kim John N. Balboa; Norchel Corcia F. Gomez; Mochamad Riza Iskandar; Muhammad Taufik Kaisupy; Swietenia Puspa Lestari; Pham Ngoc; et al. (Journal of Environmental Management, 2026)

Corrigendum to “Amorphous LaAlO3-derived electrolyte: Harnessing structural disorder for high proton conductivity in LT-CFC electrolytes” [Fuel 412 (2025) 138022] - Muhammad Ahsan Masood; Sajid Rauf; Muhammad Shahid Sharif; Zuhra Tayyab; Naveed Mushtaq; MAK Yousaf Shah; Touseef Ahmad; Atif Nazar; Bushra Bibi; Aljawhara H. Almuqrin; Abdullah N. Alodhayb; Hafsa Mansha; et al. (Fuel, 2026)

Therapeutic targeting of COX-2 in head and neck cancer: Mechanistic and clinical perspectives - Reena Gupta; Bilal Khaleel Midhin; Sabir Ali Siddiqui; Mohammad Abohassan; Pareshkumar N. Patel; Gunjan Singh; Vimal Arora; Priya Priyadarshini Nayak; Muhammad Shahid Iqbal; Zainb A. Taleb (DARU Journal of Pharmaceutical Sciences, 2026)

Expanding access to hereditary cancer genetic testing: a quality improvement initiative of mainstreaming in a diverse urban gynecology clinic - Alex Raghunandan; Lauren Davis-Rivera; Muhammad Danyal Ahsan; Isabelle R. Chandler; Steve Lopez; Amanda Laterza Ozarowski; Michelle Primiano; Christina Pardo; Ravi N. Sharaf; Melissa K. Frey (Familial Cancer, 2026)

When screentime fails: initiative to improve completion of hereditary cancer genetic testing after telemedicine counseling - Isabel R. Murray; Muhammad Danyal Ahsan; Lauren Mitchell; Siena Gioia; Michelle Primiano; Amanda Laterza Ozarowski; Tina Karimaghaie; Steve Lopez; Ravi N. Sharaf; Melissa K. Frey (Familial Cancer, 2026)

Corrigendum to “Amorphous LaAlO3-derived electrolyte: Harnessing structural disorder for high proton conductivity in LT-CFC electrolytes”. [Fuel 412 (2025) 138022. doi: 10.1016/j.fuel.2025.138022] - Muhammad Ahsan Masood; Sajid Rauf; Muhammad Shahid Sharif; Zuhra Tayyab; Naveed Mushtaq; MAK Yousaf Shah; Touseef Ahmad; Atif Nazar; Bushra Bibi; Aljawhara H. Almuqrin; Abdullah N. Alodhayb; Hafsa Mansha; et al. (Fuel, 2026)

The ongoing journey of modelling intercropping systems: A conceptual resource sharing intercomparison from model developers and expert users - Adam Muhammad Adam; Myriam Adam; Folkard Asch; Kenneth J Boote; Vimbayi Grace Petrova Chimonyo; Mathias Christina; Marc Corbeels; Antoine Couëdel; Mathilde De Freitas; Tomas Della Chiesa; Frank Ewert; Gatien N Falconnier; et al. (Field Crops Research, 2026)

Coral disease diversity and observed prevalence in the Seram Laut Islands, Indonesia - Mujiyanto Mujiyanto; Andrias S. Samusamu; Ofri Johan; Reny Puspasari; Masayu Rahmia Anwar Putri; Tirtadanu Tirtadanu; Yayuk Sugianti; Karsono Wagiyo; Muhammad Taufik; Puput Fitri Rachmawati; Prihatiningsih Prihatiningsih; Rita Rachmawati; et al. (Continental Shelf Research, 2026)

Critical habitats for sharks and rays in Asia remain largely unprotected - Adriana Gonzalez-Pestana; Peter M. Kyne; Emiliano García-Rodríguez; Ryan Charles; Vanessa Bettcher Brito; Asia O. Armstrong; Amanda Batlle-Morera; Marta D. Palacios; Christoph A. Rohner; Giuseppe Notarbartolo di Sciara; Jo Marie V. Acebes; Serena Adam; et al. (Biodiversity and Conservation, 2026)
The Asia region harbors exceptional chondrichthyan (shark, ray, and chimaera) diversity but faces intense fishing pressure. The Important Shark and Ray Areas (ISRA) process provides a collaborative, evidence-based framework to identify critical habitats and inform spatial management. We assessed ISRAs across the Bay of Bengal, Southeast Asia, and the Northwest Pacific to characterize their extent, ecological significance, and conservation relevance. We delineated 122 ISRAs spanning ~ 1 million km 2 (~ 3% of the region) across 12 jurisdictions and international waters, encompassing habitats for 121 species (~ 30% of Asia’s chondrichthyans), 76% of which are threatened. Depleted taxa (e.g., giant guitarfishes, Glaucostegidae) were represented, but charismatic megafauna (e.g., Whale Shark Rhincodon typus ) were overrepresented. In contrast, deepwater and freshwater species were underrepresented. Reproductive Areas were the most common ISRA sub-criterion applied (52% of ISRAs), largely in nearshore zones, while areas for range-restricted species were less frequently (18%) identified. Twelve ISRAs overlapped with biodiversity hotspots, including seven in areas of high overall chondrichthyan species richness and five in areas of high range-restricted species richness. Citizen science was the predominant research method used to delineate ISRAs, while fisheries data were underused despite the region’s major fisheries footprint. Geographic coverage was uneven: Indonesia held the most ISRAs (n = 40; 71.7% of ISRA coverage) while eight jurisdictions (e.g., Viet Nam, China, Republic of Korea) lacked ISRAs due to data gaps. Protection shortfalls are stark: MPAs cover

Exploring the antimicrobial potential of plant-based bioactive compounds in meat products: advances in mechanistic insights, pathogen inhibition, and shelf-life extension - Farhang Hameed Awlqadr; Mohammed N. Saeed; Ammar B. Altemimi; Syamand Ahmed Qadir; Othman Abdulrahman Mohammed; Tablo H. Salih; Aryan Mahmood Faraj; Muhammad Waqar; Hassan Raza (Critical Reviews in Food Science and Nutrition, 2026)

Amorphous LaAlO3-derived electrolyte: Harnessing structural disorder for high proton conductivity in LT-CFC electrolytes - Muhammad Ahsan Masood; Sajid Rauf; Muhammad Shahid Sharif; Zuhra Tayyab; Naveed Mushtaq; MAK Yousaf Shah; Touseef Ahmad; Atif Nazar; Bushra Bibi; Aljawhara H. Almuqrin; Abdullah N. Alodhayb; Hafsa Mansha; et al. (Fuel, 2026)

Urban vegetation loss: assessing built-up expansion and its implications on vegetation cover’s health and land surface temperature in the Accra Metropolitan Area, Ghana - Michael Batame; Emmanuel Yeboah; Elisha Njomaba; Isaac Sarfo; Selasi Klutsey; Oznur Isinkaralar; Muhammad Waseem; Ali Hasan Jaffry; Kaan Isinkaralar; Henry Adjanor Tetteh; Paul Kyeku; Ishmeal Quist; et al. (Theoretical and Applied Climatology, 2026)

Performance evaluation of single and mixed draw solutes in the forward osmosis membrane - B. E. Khan; A. Mahmood; M. Zaman; N. Muhammad; M. Shaban; S. I. Al-Saeedi; A. M. Elbasiony; W. J. Lau (International Journal of Environmental Science and Technology, 2026)

A comprehensive review of the phytochemical, and pharmacological potential of Alnus hirsuta (Spach) Rupr., (Siberian Alder): implications for anti-inflammatory therapeutics - Sajid Ali; Adnan Amin; Muhammad Saeed Akhtar; Khizar Abdullah Khan; Ishaq N. Khan; Imran Khan; Wajid Zaman; Atif Ali Khan Khalil (Inflammopharmacology, 2026)

Socio-Economic Characterization and Operational Patterns of Multi-Gear Artisanal Fisheries in Pangandaran Coastal Waters, West Java, Indonesia - Zuzy Anna; Asep A. Handaka; Lantun P. Dewanti; Nurani Khoerunnisa; Syawaluddin A. Harahap; Jogi R. N. Panggabean; Yeni Mulyani; Donny J. Prihadi; Helmalia Asri; Bagus D. Cahyo; Ripky Alfareza; Muhammad S. A. Mubarok; et al. (Fishes, 2026)
Small-scale fisheries constitute the backbone of coastal livelihoods in Indonesia, yet comprehensive socio-economic data remain limited for effective management. This study characterizes the operational and socioeconomic patterns of multi-gear artisanal fisheries in the Pangandaran coastal waters of West Java, Indonesia. A cross-sectional survey of 136 fishers across 14 coastal communities was conducted using structured questionnaires covering socio-demographic characteristics, fishing operations, and catch composition. Complete economic data were available for 125 fishermen, while multivariate analyses used n = 105 due to listwise deletion of cases with missing predictor variables. Fishermen averaged 46.9 years of age with 25.8 ± 11.6 years of fishing experience. Mean monthly income was IDR 5.80 million (SD = 7.51, 95% CI: 4.47–7.13 million, approximately USD 387). Gillnet was the dominant fishing gear (73.5% of fishermen), followed by hook-and-line (14.7%). A total of 57 fish species were recorded, dominated by hairtail Trichiurus spp. (61.0% occurrence). Statistical analyses revealed weak relationships between conventional demographic and operational variables and income. Although crew number showed a statistically significant association with income (p = 0.039), its effect size was small, and the overall regression model was not significant, with very low explanatory power (R2 = 0.038). These results indicate that income variability is largely driven by unmeasured and context-specific factors rather than observable fishing characteristics. These findings provide baseline socio-economic data essential for developing community-specific management interventions in Pangandaran waters.

Characterisation of secondary metabolites from 50% ethanol extract of ebony leaves ( Diospyros celebica Bakh.) and in vitro activity analysis of antioxidant and α-glucosidase inhibitor - Sausan Afra; Muhammad Hanafi; Esti Mumpuni; Minarti Minarti; Puspa Dewi N. Lotulung; Nina Artanti; Francis Xavier (Natural Product Research, 2026)

Review on flexible frameworks: Phosphazene functional polymers powering the future of membranes - Yasir Abbas; Muhammad Waqar Hameed; Zahid Ali; Ghulam Yasin; Kanwal Shabbir; Ijaz Hussain; Muhammad Ahsan Iqbal; Hafiz M. Adeel Sharif; Zhanpeng Wu; Nadeem Baig; Isam H. Aljundi; Niaz Ali Khan; et al. (Chemical Engineering Journal, 2026)

Green-engineered CSPVA@CuO–Ag hybrid nanocomposite for methylene blue removal: a comprehensive adsorption study - S. K. Lakkaboyana; A. Muhammad; E. A. Abdelrahman; K. Neeli; P. Venkateswarlu; R. M. N. Kalla; A. G. Alhamzani (International Journal of Environmental Science and Technology, 2026)

Spirulina supplementation and human health: An umbrella review of meta-analysis on randomized controlled trials - Nazila Soufi Amlashi; Fahad Rajab Mahmood; Mirza R. Baig; Tina Saeed Basunduwah; Pareshkumar N. Patel; Gulsara Ruziyeva; Gunjan Singh; Muhammad Shahid Iqbal; Munthar Kadhem; Amirali Ebrahimi (Algal Research, 2026)

Technological trends in rainwater harvesting for micro-hydropower: a scientometric review - S. N. F. Abdullah; M. K. A. Kamarudin; N. A. Wahab; N. Yaakub; A. S. Mohd Saudi; M. N. A. Rahman; S. Sunardi; F. Muhammad-Sukki; I. N. Ismail (International Journal of Energy and Water Resources, 2026)

Integrated plant-soil-microbiome responses mediate greenhouse gas emissions in the restoration of a semiarid steppe - Zhen Wang; Xiaojiang Yang; Paul C. Struik; Muhammad Nadeem Ashraf; Carmeron N. Carlyle; Scott X. Chang; Yuanheng Li; Wenbo Zhang; Riliga Wu; Baoming Ji; Ke Jin (Applied Soil Ecology, 2026)

Predicting the adoption peaks of oil palm agroforestry under Social Forestry Programs in Indonesia: what are the differences between commodities? - Muhammad Iqbal N. Madjid; Dwiko B. Permadi; Hero Marhaento; Budiadi; Rohman (Agroforestry Systems, 2026)

Treatment and valorization of spent caustic brine: A critical review with emphasis on membrane technologies - Rouba D. Al Bostami; Amani Al Othman; Muhammad Tawalbeh; Kerry N. McPhedran; Mohammad Mahdi A. Shirazi (Chemosphere, 2026)

Corrigendum to “Effects of full-fat black soldier fly larvae and yellow mealworm meals on blood composition and liver health in Atlantic salmon (Salmo salar)” [Aquaculture Volume 612, Part 1, 15 January 2026, 743142]. - S.M. Majharul Islam; Mette Sørensen; Muhammad A.B. Siddik; Florence Perera Willora; Monica F. Brinchmann; Kirill Spiten; Kyla Zatti; Kim D. Thompson; Ioannis N. Vatsos (Aquaculture, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Polyphenol-based therapeutics for glioblastoma: validation from In-vitro cell viability assay and integrated onco-omics computational analysis - Yogesh H S; Sadik Shaik; Sibghatullah Muhammad Ali Sangi; Krishna Swaroop; Sreeharsha Nagaraja; Anitha K N; Vipin Kumar Mishra; Santosh Prasad Chaudhary Kurmi; Subrata Nath; Shankar Thapa (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

A systematic literature review on evaluation of microbial fuel cell in bioremediating toxic compounds from wastewater sludge - M. A. F. Muhammad Lukman; A. M. Ahmad Mokhtar; A. S. Yaakop; M. Mohd Zaini Makhtar; N. A. Kamaruzaman (International Journal of Environmental Science and Technology, 2026)
The escalating concerns over environmental pollution that is severe and the need for sustainable waste treatment methods have driven significant attention toward finding innovative technological solutions. Microbial fuel cell (MFC) has been identified as a potential approach for sludge treatment and renewable energy production. The MFC is a bio-electrochemical system that is promising environmental remediation technology due to its simple compact design, low cost and renewable energy production. As MFC is a recently developed and emerging technology, limited studies have been reported to provide complete and inclusive analyses. This Systematic Literature Review (SLR) aims to provide a comprehensive evaluation of the efficacy of MFC in the bioremediation of toxic compounds from wastewater sludge. The process of writing this SLR has adhered to the PRISMA (Preferred Reporting Items for Systematic Review and Meta-Analysis) writing standard. To search for relevant articles and sources to be included in this SLR, three main databases, namely PubMed, Web of Science and Scopus were utilized with studies spanned from 2003 to 2023. Various types of MFC were evaluated for their bioremediation properties and from the extensive analysis conducted, it could be deduced that dual-chamber MFC is the most effective method of bioremediation due to the presence of two separate chambers. Referring to this SLR, it supports the effectiveness of MFC in bioremediating toxic compounds present in wastewater sludge. In addition, the microbial processes within MFC contribute significantly to the removal or reduction of various contaminants. Graphical abstract

Natural products as HMG-CoA reductase inhibitors (statins) for the management of non-communicable diseases - Radwa N. Muhammad; Nora M. Aborehab; Shaza H. Aly; Noha N. Nasr; Merhan O. Hindam; Aya M. Mustafa; Safaa A. Faheem; Mariam H. Fawzy; Mohammed E. Abo-El Fetoh; Ahmed M. El-Dessouki; Mostafa A. Rabie; Riham A. El-Shiekh; et al. (Inflammopharmacology, 2026)
Non-communicable diseases, such as diabetes, cancer, as well as cardiovascular, metabolic, and central nervous system disorders stand for significant global health burden. Statins, as HMG-CoA reductase inhibitors, have emerged as a basis in the management of hypercholesterolemia and the prevention of cardiovascular disorders. In this review, we summarize the role of statins in a variety of pathologies, ranging from their well-recognized effects in cardiovascular disorders, to the newly revealed favorable effects in cancer, eye, autoimmune, kidney, gastrointestinal, bone, and autoimmune disorders. Additionally, the current review explores insights into the potential role of natural products as HMG-CoA reductase inhibitors. Future research should focus on the synergistic effects of natural therapies with synthetic statins to improve health outcomes in populations burdened by non-communicable diseases.

Effects of full-fat black soldier fly larvae and yellow mealworm meals on blood composition and liver health in Atlantic salmon (Salmo salar) - S.M. Majharul Islam; Mette Sørensen; Muhammad A.B. Siddik; Florence Perera Willora; Monica F. Brinchmann; Kirill Spiten; Kyla Zatti; Kim D. Thompson; Ioannis N. Vatsos (Aquaculture, 2026)

Photocatalytic Degradation of Synozol Navy Blue Dye Using Ni-Ag Co-doped ZnO: Optimization, Mechanistic, Scavenging and Kinetics Studies - Zahid Mehmood; Muhammad Alamzeb; Tahseen Ghous; Sidra Rashid; Zulfiqar Ali; Muhammad Haseeb; Sabah Ansar; William N. Setzer (Journal of Fluorescence, 2025)

Corrigendum to “Microplastic assessment in remote and high mountain lakes of Gilgit Baltistan, Pakistan” [Chemosphere 365 (2024) 143283] - Maryem Mehboob; Rachid Dris; Bruno Tassin; Johnny Gasperi; Muhammad Usman Khan; Riffat N. Malik (Chemosphere, 2025)

Corrigendum to “Mucosal barrier status in Atlantic salmon fed rapeseed oil and Schizochytrium oil partly or fully replacing fish oil through winter depression” [Fish Shellfish Immunol. 149 (2024) 109549] - SM Majharul Islam; Florence Perera Willora; Mette Sørensen; Golam Rbbani; Muhammad A.B. Siddik; Kyla Zatti; Shruti Gupta; Ian Carr; Ester Santigosa; Monica F. Brinchmann; Kim D. Thompson; Ioannis N. Vatsos (Fish & Shellfish Immunology, 2025)

Growth phenology, cambial activity, and formation of secondary vascular tissues in Juniperus procera trees - Pervaiz R. Khan; Rahmah N Al-Qthanin; Ibrahim M. Aref; Muhammad Iqbal (Flora, 2025)

Energy transport in ternary hybrid nanofluid with variable thermal conductivity under the combined effects of electroviscous, electric potential, and heat generation - Shafiq Ahmad; Aamir Abbas Khan; Muhammad Naveed Khan; Salah Knani; N. Ameer Ahammad; Ibrahim E. Elseesy (Dynamics of Atmospheres and Oceans, 2025)

Experimental study on stability, rheology, and CO2 storage capacity of polymer-enhanced foams in carbonates - Muhammad Mushtaq; Mudassar Mumtaz; Emad W. Al-Shalabi; Waleed Alameri; Georgios N. Karanikolos; Stefan Iglauer (Chemical Engineering Journal, 2025)

Reactive oxygen species production and signal transduction in response to stress triggered by Alternaria elicitors in Brassicaceae - Sana Munir; Ahmad N. Shahzad; Avanish Rai; Veselin Petrov; Tsanko Gechev; Sajid Shokat; Muhammad K. Qureshi (Plant Molecular Biology, 2025)

Molecular characterization and cuticular stomatal anatomy of Punica Granatum L. cultivars study in Dohuk governorate - Dalal Y. Kh. Sinjare; Shamiran S. Abdulrahman; Nizek S. Khalid; Rizgar Y. Ismail; Muhammad Yasir Naeem; Zeliha Selamoglu; Gani Issayev; Aveen M. N. Ahmed (Molecular Biology Reports, 2025)

Exome sequencing in a Pakistani male infertility cohort: perspective on molecular diagnosis, genetic heterogeneity, and diagnostic yield - Dapeng Zhou; Ambrin Fatima; Afrasiab Ahmed; Tehseen Ullah Khan Afridi; Haq Nawaz Khan; Mussarat Ashraf; Muhammad Naeem; Syed Babar Jamal; Ishtiaq Hassan; Erica E. Davis; Feng Zhang; Rehana Rehman; et al. (Molecular Genetics and Genomics, 2025)

Enhanced stability and coke resistance in methanol to olefins reaction using fibrous silica-wrapped silicoaluminophosphate zeolite - Muhammad Hafizuddin Mohd Sofi; Muhamed Yusuf Shahul Hamid; Aishah Abdul Jalil; Tuan Amran Tuan Abdullah; Mohamed Yusuf Mohamud; Mahadi Bahari; Nurul Sahida Hassan; Dai-Viet N. Vo (Environmental Chemistry Letters, 2025)

Masked autoencoder-based vision framework for robust fire detection in complex environments - Hanxiang Wang; Muhammad Fayaz; Awais Ahmad; Yanfen Li; Tan N. Nguyen; L. Minh Dang (Process Safety and Environmental Protection, 2025)

Utilization of the desalination brine for enhancing inland shrimp farming in Kuwait - Sherain N. Al-Subiai; In Kwon Jang; Sumaiah Hussain; Enas Al-Hasan; Muhammad Al-Foudari; Ali Al-Odwani; Sarah Al-Jutaili; Tae-Jin Choi (Desalination, 2025)

Glyceraldehyde-3-phosphate dehydrogenase facilitates Mycoplasma synoviae colonisation in the lower respiratory system - Sahar Zare; Marc S. Marenda; Sathya N. Kulappu Arachchige; Pollob Shil; Muhammad A. Shahid; Somayeh Kordafshari; Chathuri H. Rodrigo; Amin Kawarizadeh; Denise O’Rourke; Amir H. Noormohammadi (Veterinary Microbiology, 2025)

Unraveling Quaternary travertine precipitation through new sedimentological and geochemical insights at Kurkur Oasis, Egypt - Kamal Abou Elmagd; Al-Hussein M. Fathy; Russell N. Drysdale; Wael Abdelwahab; Muhammad Hazem; Mohammed Hassan Younis (Geomorphology, 2025)

Enhanced Photocatalytic Degradation of Methyl Red Dye with Bismuth-Doped ZnO: Kinetics, Mechanistic and Re-cyclability Aspects - Muhammad Alamzeb; Noor-ul-Ain Zulfiqar; Muhammad Faran Akhtar; Iqra Riaz; Faiza Ameen; Aqib Asghar; William N. Setzer (Journal of Fluorescence, 2025)

Phenology of coastal upwelling in the Southeastern Arabian Sea: Insights from in-situ and satellite observations - Shirin J Jadhav; Muhammad Shafeeque; V S Arun; N N S Vishnu; B R Smitha (Journal of Earth System Science, 2025)

Activation of Sig-1R by afobazole attenuates Tollip/HMGB1-mediaded CCN2 autophagic degradation and NETs formation in sunitinib-induced cardiotoxicity in mice: Involvement of IRE 1α/ASK1/JNK/ AP-1 trajectory - Marihan S. Shafik; Dalia M. El-Tanbouly; Abeer Bishr; Ayman A. Soubh; Amina S. Attia; Radwa N. Muhammad (Toxicology and Applied Pharmacology, 2025)

Nature-inspired bio-composites for phosphate sequestration and recovery: Green synthesis, mechanistic insights, and multi-stage optimization - Hafiz Muhammad Umer Aslam; Saurabh Singh; Mohiuddin Quadir; Achintya N. Bezbaruah (Science of The Total Environment, 2025)

Time series data analysis to predict the status of mastitis in dairy cows by applying machine learning models to automated milking systems data - Muhammad N. Dharejo; Lukas Minogue; Tina Kabelitz; Thomas Amon; Olivier Kashongwe; Marcus G. Doherr (Preventive Veterinary Medicine, 2025)

Long-term fertilization with crop residue management enhances soil structure and the yield of sweet potato by optimizing soil organic carbon and acidity - Imtiaz AHMED; Jing HUANG; Jiwen LI; Nano A. DABA; Zhe SHEN; Kiya A. TADESSE; Mahmoud ABDELAZIZ; Md A. ALAM; Muhammad N. KHAN; Philip T. SINGBAH; Jun YAN; Huimin ZHANG (Pedosphere, 2025)

Effect of selenium, sonication, and combination of selenium and sonication treatments on potassium bromate, alloxan, and titanium dioxide in bread - Sana Gammoh; Muhammad H. Alu'datt; Mohammad N. Alhamad; Taha Rababah; Mohammad Alrosan; Malak Shatarah (Food Chemistry, 2025)

Electrochemical activation of alum sludge for the adsorption of lead (Pb(II)) and arsenic (As): Mechanistic insights and machine learning (ML) analysis - Hye-Bin Kim; Muhammad Fahad Ehsan; Akram N. Alshawabkeh; Jong-Gook Kim (Bioresource Technology, 2025)

Anti-arthritic potential of linalool: in vitro, in vivo, and in silico mechanistic insights for safer therapeutic applications - Shoyaeb Ahammed; Raihan Chowdhury; Md. Sakib Al Hasan; Emon Mia; Md. Showkoth Akbor; Md. Tahajul Islam; Rokibul Islam Chowdhury; Md. Sabbir Hossain; Irfan Aamer Ansari; Siddique Akber Ansari; Md. Amirul Islam; Zainab M. Almarhoon; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Numerical modelling of vadose zone flow for a shallow groundwater wetland using HYDRUS-1D - Muhammad Usman; Lloyd H. C. Chua; Kim N. Irvine; Lihoun Teang (Modeling Earth Systems and Environment, 2025)
This study employs HYDRUS-1D for modelling the vadose zone processes in a shallow groundwater wetland. HYDRUS-1D is based on Richards equation whose numerical solution heavily relies on reliable data derived from soil water retention curves. This modelling was supported by extensive field and laboratory measurements. Both disturbed and undisturbed soil samples were collected at the four depths for determination of particle size distribution, bulk density, saturated hydraulic conductivity, and saturated water content. The van Genuchten retention curves were used to describe the relationship between pressure head and water content; model parameters were optimized through inverse modelling with initial estimates of residual water content, shape parameters (α and n) obtained from ROSETTA model 3 (provided in HYDRUS-1D) and saturated water content and saturated hydraulic conductivity, determined from laboratory tests. Independent measurements of soil moisture and soil tension measured both in the field and laboratory fit well with the water retention curve obtained from the optimized ROSETTA parameters. Model performance in simulating measured water contents was good (average RMSE = 0.02 m 3 /m 3 ) during calibration and validation (0.01 m 3 /m 3 and 0.03 m 3 /m 3 for two independent periods). Water content in upper soil layers was strongly influenced by atmospheric conditions, while groundwater level has the most influence in the bottom layers. Evapotranspiration was found out to be the dominant process in summer with total flux higher than that of infiltration while in winter evapotranspiration was relatively lower, even though still higher than infiltration.

Long-term trends in heavy metal contamination of marine sediments in the Arabian Gulf: A meta-analysis - S. Swetha; S. Veerasingam; S. Rajendran; Hassan Hassan; Muhammad Zia U. R. Rahman Hashmi; Hamood Alsaadi; Nelson Rangel-Buitrago; Fadhil N. Sadooni (Environmental Monitoring and Assessment, 2025)
Heavy metal (HM) contamination in marine sediments is a critical environmental concern due to its potential ecological and human health impacts. This study provides a comprehensive assessment of the spatial and temporal evolution of HM contamination in Arabian Gulf sediments over a 33-year period (1991–2024). Contamination levels were evaluated using key sediment quality indices such as the contamination factor (CF), geoaccumulation index (I g ₑₒ), pollution load index (PLI), and ecological risk index (ERI) based on available meta-data. Spatial analysis revealed that marine sediments along the Iranian and Saudi Arabian coasts exhibited higher contamination levels compared to those of other Gulf countries. This elevated contamination is likely attributed to industrial discharges, oil spills and effluent releases from desalination plants. Arsenic (As), cadmium (Cd), copper (Cu), nickel (Ni), and lead (Pb) emerged as the primary toxic contributors to sediment pollution. Overall, HM contamination status in the region is predominantly low to moderate, with localized hotspots near industrialized coastal zones. The study highlights the need for scientifically informed waste management strategies to mitigate HM contamination, particularly in nearshore environments impacted by industrial activities. Furthermore, it recommends the implementation of continuous monitoring programs to track temporal trends and identify emerging contamination sources. These findings provide critical insights for environmental managers and policymakers in developing sustainable pollution mitigation frameworks and enhancing the resilience of marine ecosystems in the Arabian Gulf.

Geological and geochemical evolution of the Derhib sulfide-talc deposit in the South Eastern Desert, Egypt: Insights into ore genesis and metasomatic alteration - Mohamed Faisal; Huan Li; Rub'son N'nahano Heritier; Muhammad A. Gul; Farah A. Khedr; Zhekai Zhou; Sobhi M. Ghoneim (Lithos, 2025)

Genetic determinants of heat content in chile pepper (Capsicum spp.) revealed by multi-locus genome-wide association mapping - Muhammad Ibrar Khan; Dennis N. Lozada; Amol N. Nankar; Ehtisham S. Khokhar; Seyed Shahabeddin Nourbakhsh (Euphytica, 2025)

Simultaneous removal of Cr(VI), As(III), and sulfanilamide via an e-barrier electrochemical system: A pilot study - Jong-Gook Kim; Muhammad Fahad Ehsan; Akram N. Alshawabkeh; Kitae Baek (Journal of Hazardous Materials, 2025)

Low molecular weight peptides of black sea cucumber (Holothuria atra) down-regulate MMP-1 in human dermal fibroblasts - Ariyanti S. Dewi; Gintung Patantis; Tiara S. Khatulistiani; Muhammad Nursid; Nurrahmi D. Fajarningsih; Yusro N. Fawzya; Hanifah N. Lioe (Food Bioscience, 2025)

Tailoring g-C3N4 properties through P and K co-doping: advancing photocatalytic CO2 reduction to CH4 - Ahmed Ismail; Muhammad Zahid; Bilal Ahmad; Salman Hayat; Sher Ali; Syed ul Hasnain Bakhtiar; Abdullah N. Alodhayb; Xiaoqiang Wu; Qaisar Alam; Sharafat Ali; Liang Qiao (Chemical Engineering Journal, 2025)

Genetic and Population Diversity of Temnocephalids Associated with the Invasive Crayfish Cherax quadricarinatus in Malaysia - Norhan N. Azri-Shah; Nor Asma Husna Yusoff; Farizan Abdullah; Ahmad Najmi Ishak; Norainy Mohd Husin; Hin Boo Wee; John Brian Jones; Muhammad Ikhwanuddin; Siti Azizah Mohd Nor; Marina Hassan (Acta Parasitologica, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Occurrence of aflatoxins and effect of preventive practices to inhibit fungal growth and aflatoxin production in leftover flat bread/chapati used as animal feed and stored in Pakistani dairy farms - Mavra Amin; Amir Ismail; Iqra Naeem; Usama Nasir; Muhammad Riaz; Yun Yun Gong; Sher Ali; Michael N. Routledge; Amna Iqbal; Asifa Saif; Carlos Augusto Fernandes Oliveira (Journal of Stored Products Research, 2025)

Eucalyptol attenuates indomethacin-induced gastric ulcers in rats by modulating the ICAM-1, eNOS and COX/LOX pathways: Insights from in silico, in vitro and in vivo approaches - Urooj Iqbal; Abdul Malik; Nabeela Tabassum Sial; Malik Hassan Mehmood; Ambreen Malik Uttra; Ume Ruqia Tulain; Alia Erum; Muhammad Fayyaz-ur-Rehman; Nermeen N. Welson; Mohamed H. Mahmoud; Athanasios Alexiou; Marios Papadakis; et al. (Food and Chemical Toxicology, 2025)

Unveiling the anxiolytic and analgesic effects of citronellal in Swiss mice: in vivo and in silico insights into COX and GABAA receptor pathways - Muhammad Torequl Islam; Md. Sakib Al Hasan; Raihan Chowdhury; Emon Mia; Imam Hossen Rakib; Noshin Tasnim Yana; Heba A. S. El-Nashar; Siddique Akber Ansari; Irfan Aamer Ansari; Md. Amirul Islam; Zainab M. Almarhoon; William N. Setzer; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Using DNA metabarcoding to assess insect diversity in grasslands - Changjin Lin; Haibin Han; Kejian Lin; Hongmei Cheng; Luyao Fu; Muhammad Ashfaq; Paul D. N. Hebert; Chenxi Liu (Applied Entomology and Zoology, 2025)

Growth Patterns Between Ages 0 and 36 Months Among US Children With Orofacial Cleft: A Retrospective Cohort Study - Christy M. McKinney; Waylon Howard; Kiley Bijlani; Muhammad Rahman; Anna Meehan; Kelly N. Evans; Dawn Leavitt; Thomas J. Sitzman; Peter Amoako-Yirenkyi; Carrie L. Heike (Journal of the Academy of Nutrition and Dietetics, 2025)

Upcycling of post-consumer mixed polyolefin feedstock: An economic and technical evaluation - Tyler N. Johnson; Jason DesVeaux; Arpit Bhatt; Rishi Sharma; Tanyaradzwa Muzata; Muhammad Rabnawaz (Journal of Environmental Management, 2025)

Pathology of an unusual outbreak of fatal disease associated with mycobacterial and Pseudomonas aeruginosa infections and intracytoplasmic inclusion bodies in juvenile spectacled caimans (Caiman crocodilus) - Sufiah U.N.K. Azlin; Nurul F. Muhammad Husairy; Charisha Fraser; Nurul I.U. Zahli; Mohd N. Akmal; Annas Salleh (Journal of Comparative Pathology, 2025)

Exploring Green Practices: a Review of Carbon Dot-Based Sustainable Sensing Approaches - Kawan F. Kayani; Sewara J. Mohammed; Nian N. Mohammad; Mohammed K. Rahim; Muhammad S. Mustafa; Harez Rashid Ahmed; Wrya O. Karim; Mohammed K. Sidiq; Shujahadeen B. Aziz (Journal of Fluorescence, 2025)

Photocatalytic Degradation of Brilliant Blue Dye Under Solar Light Irradiation: An Insight Into Mechanistic, Kinetics, Mineralization and Scavenging Studies - Muhammad Alamzeb; Sabahat Faryad; Ihsan Ullah; Javeed Hussain; William N. Setzer (Journal of Fluorescence, 2025)

Impact of rising temperatures on scavenging chicken production in Uganda: farmer perceptions, challenges and coping strategies - Zainah Nampijja; Sadhat S. Walusimbi; Emmanuel Zziwa; Donald R. Kugonza; Muhammad Kiggundu; Kanifa Kamatara; Gorettie N. Nabanoga; Yazidhi Bamutaze; Charlotte J. Nakakaawa; Lein Haakon (Tropical Animal Health and Production, 2025)

Correction: Polychlorinated biphenyls induced toxicities upon cell lines and stem cells: a review - Muhammad Zaffar Hashmi; Anaela Shoukat; Siwatt Pongpiachan; Yasar N. Kavil; Saeed Saad Alelyani; Mohammed M. Alkasbi; Mohamed Hussien; Md Toushik Ahmed Niloy (Environmental Geochemistry and Health, 2025)

A global review on perfluoroalkyl acids (PFAAs) in the riverine systems: Environmental behaviours and risks implications - Muhammad Younas; Kifayatullah Khan; Maria Zeb; Muhammad Yaseen; Noor Samad Shah; Hassan Alshemmari; Yasar N. Kavil; Saeed Saad Alelyani; Mohamed Hussien; Sidra Zeb; Di Du (Science of The Total Environment, 2025)

Pathways and risk analysis of arsenic and heavy metal pollution in riverine water: Application of multivariate statistics and USEPA-recommended risk assessment models - Kifayatullah Khan; Muhammad Sajawal Khan; Muhammad Younas; Muhammad Yaseen; Abdullah G. Al-Sehemi; Yasar N. Kavil; Chao Su; Niaz Ali; Afsheen Maryam; Ruoyu Liang (Journal of Contaminant Hydrology, 2025)

Estimating water surface elevation for a wetland using integrated multi-sourced remote sensing data - Muhammad Usman; Lloyd H. C. Chua; Kim N. Irvine; Lihoun Teang (Wetlands Ecology and Management, 2025)
Surface water plays an important role in understanding the hydrological behaviour of a wetland and is crucial for the sustainability of wetland ecosystems. Remote sensing increasingly is used for the estimation of surface water levels in larger inland waterbodies. However, there are few investigations that have employed multi-sourced remote sensing data for water level predictions in wetlands, which was the motivation for undertaking this study. Sentinel-2 and Landsat-8 are among the latest satellites providing optical imagery with high spatial resolution and coverage that are available in the public domain. Different water indices have been applied to estimate surface water levels using these satellite image sources; however, what index to use for a particular application requires thorough, site-specific analysis. In this study, the Normalized Difference Water Index (NDWI), two versions of the Modified Normalized Difference Water Index (MNDWI), and the Water Ratio Index (WRI) were used to estimate water levels in a constructed wetland, as part of an effort to better guide regulation and decision-making for a local management agency. The satellite data were complemented with high resolution aerial photogrammetric images and LiDAR data to assess the accuracy of water level predictions provided by the satellite images. The photogrammetric images were used as reference datasets while the LiDAR data supported the development of area-elevation curves for the wetland. Accuracy assessment between the satellite and reference images was performed using the Kappa co-efficient (K). MNDWI performed better than the other water indices for both satellite data sources; however, the optimum threshold was different for each satellite (− 0.35 for Sentinel-2 and − 0.25 for Landsat-8). K values for the optimum threshold ranged between 0.72 and 0.77 for Sentinel-2 and 0.73 and 0.87 for Landsat-8. The water levels estimated using the remotely sensed data were assessed against in situ, continuously measured water levels using multiple efficiency evaluation metrics including R 2 , RMSE, and SSE. Estimated water levels with Sentinel-2 and Landsat-8 resulted in an R 2 of 0.86 and 0.88, RMSE of 0.04 m and 0.06 m, and an SSE of 0.02 m and 0.06 m, respectively. These results show that even for a small wetland, it is possible to use satellite imagery to estimate water levels with high accuracy.

Development of a genotype-matched Newcastle disease DNA vaccine candidate adjuvanted with IL-28b for the control of targeted velogenic strains of Newcastle disease virus in Africa - Charlie F. Amoia; Augustino A. Chengula; Jean N. Hakizimana; Philemon N. Wambura; Muhammad Munir; Gerald Misinzo; James Weger-Lucarelli (Veterinary Research Communications, 2025)
Newcastle disease virus (NDV) is an extremely contagious and deadly virus that affects numerous bird species, posing serious threats to poultry production on a global scale. In addition to implementing biosecurity practices in farming systems, vaccination remains the most effective means of controlling Newcastle disease (ND). However, while existing commercial vaccines provide some level of protection, the effectiveness of these vaccines can be questionable, particularly in field settings where the complexity of vaccination program implementation poses significant challenges, especially against virulent genotypes of NDV. A genotype-matched NDV DNA vaccine could potentially offer a more effective vaccination approach than currently available live attenuated vaccines. By being specifically tailored to match circulating strains, such a vaccine might improve efficacy and reduce the risk of vaccine failure due to genotype mismatch. To develop an alternative vaccine approach, two ND DNA vaccines were constructed in this study. Each vaccine developed in this study contains the fusion (F) and haemagglutinin-neuraminidase (HN) genes of a virulent NDV genotype VII isolate from Tanzania. Interferon lambda-3 (IFNλ3; IL-28b), which has demonstrated capacity to significantly enhance specific adaptive immune responses and decreased levels of inflammatory cytokines, as well as improved protective responses at a high viral challenge dose, was included in one of the developed vaccines. These plasmids were designated pTwist-F-HN-VII-IL28b and pTwist-F-HN-VII. The two plasmids differed in that pTwist-F-HN-VII-IL28b contained the cytokine adjuvant IL-28b. Transfection of cells and subsequent immunofluorescence assays indicated that both plasmids expressed high levels of NDV F-HN proteins. In vivo immunization demonstrated that chicks intramuscularly immunized with pTwist-F-HN-VII-IL28b exhibited significant immune responses compared to chicks immunized with pTwist-F-HN-VII or the commonly used LaSota vaccine (LaSota), which was used as a control. The protective efficacy of pTwist-F-HN-VII-IL28b was 80% after challenge with the highly virulent NDV strain ON148423, compared to 60% for chicks vaccinated using LaSota, and pTwist-F-HN-VII. The findings of this study indicate that IL-28b can be employed as a molecular adjuvant for NDV vaccines. This study represents a key milestone in Newcastle disease vaccine research, particularly in the development of a genotype-matched DNA vaccine candidate. Additionally, this study demonstrated that the combination of F, HN, and IL-28b elicits an efficacious immune response against virulent NDV strains.

Polychlorinated biphenyls induced toxicities upon cell lines and stem cells: a review - Muhammad Zaffar Hashmi; Anaela Shoukat; Siwatt Pongpiachan; Yasar N. Kavil; Saeed Saad Alelyani; Mohammed M. Alkasbi; Mohamed Hussien; Md Toushik Ahmed Niloy (Environmental Geochemistry and Health, 2025)

Nutraceutical Impact of Pumpkin Seed Oil on Expression Levels of EZH-2 and KRT-14 Genes against DSS-induced Inflammatory Bowel Disease in the Rat Model - Asma Mukhtar; Imran Mukhtar; Humaira Muzaffar; Muhammad Naeem Faisal; Kashif ur rehman khan; Laaraib Nawaz; Muhammad Umar Ijaz; Sana Maryam; Muhammad Umair; Haseeb Anwar; Farid S. Ataya; Gaber El-Saber Batiha; et al. (Cell Biochemistry and Biophysics, 2025)
Inflammatory bowel disease is a collection of intestinal disorders that cause inflammation in the digestive tract. Prolonged inflammation in the gastrointestinal tract is a major risk factor for colorectal cancer. The objective of this study was to fucus on gene expression levels of ( KRT-14 ; associated with epithelial cell integrity) and enhancer of zeste homolog-1 ( EZH-2; involved in cellular proliferation) in a IBD rat model in order to rule out impact of nutraceuticals (pumpkin seed oil; PSO) as a complementary approach to conventional treatments of IBD. In the current study, IBD was induced using dextran sodium sulfate (DSS). Following acclimatization, rats were separated into three groups: the negative control, the positive control, and the treatment group. The DSS (1 ml/kg bw) was given to the positive control and treatment groups. Negative control was given only a normal diet. Pumpkin seed oil (PSO) was given orally as a treatment (0.5 ml/kg bw). Blood and colon tissue were obtained on the 5 th , 10 th , 14 th, and 18 th days. Physical parameters, hematology, biochemical assays, gene expression, and histopathology were carried out. After statistical analyses, macroscopic parameters showed significant differences. Biochemical analyses revealed a significant ( P ≤ 0.05) decrease in serum potassium concentrations, total cholesterol, triglycerides, total proteins, total oxidants status, and C-reactive proteins in PSO treated group as compared with positive control. Gene expression levels of KRT-14 and EZH2 were significantly ( P ≤ 0.05) upregulated in PSO treated group as compared to positive control group. Histopathology revealed that pumpkin seed oil preserved the structural integrity of colon.

Enhancing the performance of Litopenaeus vannamei nursery and grow-out by modifying Mg/Ca ratios in biofloc systems using low-salinity groundwater of Kuwait Desert - Sherain N. Al-Subiai; In Kwon Jang; Sun-Hye Bae; Hong-seok Yoon; Sumaiah Hussain; Sabeekah AlNuaimi; Muhammad Al-Foudari; Enas Al-Hasan (Aquaculture, 2025)

Assessing the concentration, distribution and characteristics of suspended microplastics in the Malaysian indoor environment - M. Dewika; Kalaimani Markandan; Shalini Nagaratnam; N. Ahmad Irfan; Muhammad Amirul Aizat Mohd Abdah; J. Nor Ruwaida; Y.Y. Sara; Mohammad Khalid (Science of The Total Environment, 2025)

Fishing event detection and species classification using computer vision and artificial intelligence for electronic monitoring - Muhammad Saqib; Muhammad Rizwan Khokher; Xin Yuan; Bo Yan; Douglas Bearham; Carlie Devine; Candice Untiedt; Toni Cannard; Kylie Maguire; Geoffrey N. Tuck; L. Rich Little; Dadong Wang (Fisheries Research, 2024)

Earthworms as Catalysts for Climate-Resilient Agriculture: Enhancing Food Security and Water Management in the Face of Climate Change - Muhammad Danish Toor; Abdul Basit; Benedict Okorie; Dibyajyoti Nath; Muhammad Mughees Ud Din; Pawan Kumar Verma; Saleem Sajjad; Izhar Ullah; Hany N. Yousef; Heba I. Mohamed (Water, Air, & Soil Pollution, 2024)

Empagliflozin-activated AMPK elicits neuroprotective properties in reserpine-induced depression via regulating dynamics of hippocampal autophagy/inflammation and PKCζ-mediated neurogenesis - Radwa N. Muhammad; Mohammed A. Albahairy; Mai A. Abd El Fattah; Weam W. Ibrahim (Psychopharmacology, 2024)
Rationale Major depression has been an area of extensive research during the last decades, for it represents a leading cause of disability and suicide. The stark rise of depression rates influenced by life stressors, economic threats, pandemic era, and resistance to classical treatments, has made the disorder rather challenging. Adult hippocampal neurogenesis and plasticity are particularly sensitive to the dynamic interplay between autophagy and inflammation. In fact, the intricate balance between the two processes contributes to neuronal homeostasis and survival. Objectives Having demonstrated promising potentials in AMPK activation, a major metabolic sensor and autophagy regulator, empagliflozin (Empa) was investigated for possible antidepressant properties in the reserpine rat model of depression. Results While the reserpine protocol elicited behavioral, biochemical, and histopathological changes relevant to depression, Empa outstandingly hindered these pathological perturbations. Importantly, hippocampal autophagic response markedly declined with reserpine which disrupted the AMPK/mTOR/Beclin1/LC3B machinery and, conversely, neuro-inflammation prevailed under the influence of the NLRP3 inflammasome together with oxidative/nitrative stress. Consequently, AMPK-mediated neurotrophins secretion obviously deteriorated through PKCζ/NF-κB/BDNF/CREB signal restriction. Empa restored hippocampal monoamines and autophagy/inflammation balance, driven by AMPK activation. By promoting the atypical PKCζ phosphorylation (Thr403) which subsequently phosphorylates NF-κB at Ser311, AMPK successfully reinforced BDNF/CREB signal and hippocampal neuroplasticity. The latter finding was supported by hippocampal CA3 toluidine blue staining to reveal intact neurons. Conclusion The current study highlights an interesting role for Empa as a regulator of autophagic and inflammatory responses in the pathology of depression. The study also pinpoints an unusual contribution for NF-κB in neurotrophins secretion via AMPK/PKCζ/NF-κB/BDNF/CREB signal transduction. Accordingly, Empa can have special benefits in diabetic patients with depressive symptoms. Limitations The influence of p -NF-κB (Ser311) on NLRP3 inflammasome assembly and activation has not been investigated, which can represent an interesting point for further research. Graphical abstract

Exome sequencing in four families with neurodevelopmental disorders: genotype–phenotype correlation and identification of novel disease-causing variants in VPS13B and RELN - Tehseen Ullah Khan Afridi; Ambrin Fatima; Humayoon Shafique Satti; Zaineb Akram; Imran Khan Yousafzai; Wajahat Bin Naeem; Nasreen Fatima; Asmat Ali; Zafar Iqbal; Ayaz Khan; Muhammad Shahzad; Chunyu Liu; et al. (Molecular Genetics and Genomics, 2024)

Snow leopard phylogeography and population structure supports two global populations with single refugial origin - Imogene A. Cancellare; Byron Weckworth; Anthony Caragiulo; Kristine L. Pilgrim; Thomas M. McCarthy; Alisher Abdullaev; George Amato; Xiaoxing Bian; Elena Bykova; Isabela Dias-Freedman; Mariya Gritsina; Lauren M. Hennelly; et al. (Biodiversity and Conservation, 2024)
Snow leopards ( Panthera uncia ) inhabit the mountainous regions of High Asia, which experienced serial glacial contraction and expansion during climatic cycles of the Pleistocene. The corresponding impacts of glacial vicariance may have alternately promoted or constrained genetic differentiation to shape the distribution of genetic lineages and population structure. We studied snow leopard phylogeography across High Asia by examining range-wide historical and contemporary genetic structure with mitochondrial DNA and microsatellite markers. We genotyped 182 individuals from across snow leopard range and sequenced portions of the mitogenome in a spatially stratified subset of 80 individuals to infer historical biogeographic and contemporary patterns of genetic diversity. We observed a lack of phylogeographic structure, and analyses suggested a single refugial origin for all sampled populations. Molecular data provided tentative evidence of a hypothesized glacial refugia in the Tian Shan-Pamir-Hindu Kush-Karakoram mountain ranges, and detected mixed signatures of population expansion. Concordant assessments of microsatellite data indicated two global genetic populations, though we detected geographic differences between historical and contemporary population structure and connectivity inferred from mitochondrial and microsatellite data, respectively. Using the largest sample size and geographic coverage to date, we demonstrate novel information on the phylogeographic history of snow leopards, and corroborate existing interpretations of snow leopard connectivity and genetic structure. We recommend that conservation efforts incorporate genetic data to define and protect meaningful conservation units and their underlying genetic diversity, and to maintain the snow leopard’s adaptive potential and continued resilience to environmental changes.

Earthworm, Perionyx excavatus as an alternate protein source for Nile tilapia: Effects on growth performance, blood biochemistry, erythrocyte morphology and intestinal health - Bethi Das; S. M. Majharul Islam; Sudipta Kumar Nag; Al-Azim; Ioannis N. Vatsos; Muhammad A. B. Siddik (Aquaculture International, 2024)
Recently, an increasing disparity has emerged in the need for raw fish meal (FM) and its supply, along with the environmental and financial obstacles associated with its use. Therefore, increasing and elevating the diversity of alternative protein sources for aquaculture nutrition is imperative. The study investigated the impact of substituting FM protein with EW meal on the growth, haemato-biochemical response and intestinal histomorphology of Nile tilapia. Up to 20% fishmeal replacement with EW meal had no adverse effects on fish growth performance. A quadratic analysis of the final body weight and EW meal level indicated the best growth performance at 17.5% replacement. Fish fed the 40% replacement level had significantly decreased height and width of intestinal folds and number of mucosal goblet cells compared to the control. Although red and white blood cell counts were found unchanged between the control, the 10% and 20% replacement groups, a significantly higher number of white blood cells and a lower number of red blood cells were found in the 40% group compared to the control. Blood glucose level was the highest, while haemoglobin level was the lowest in the 40% group. In the same group, significantly higher frequencies of erythrocyte cellular and nuclear abnormalities were noted. Lipid droplet accumulation in the liver was significantly higher in the 40% group, whilst the 10% and 20% groups showed no significant difference compared to the control.

A comprehensive review of remediation strategies for mitigating salt precipitation and enhancing CO2 injectivity during CO2 injection into saline aquifers - Victor Darkwah-Owusu; Muhammad Aslam Md Yusof; Yen A. Sokama-Neuyam; Joshua N. Turkson; Ingebret Fjelde (Science of The Total Environment, 2024)

Assessing the electrode configuration in a sandbox system for the removal of sulfanilamide: A pilot study - Jong-Gook Kim; Hye-Bin Kim; Muhammad Fahad Ehsan; Akram N. Alshawabkeh; Kitae Baek (Chemosphere, 2024)

Microplastic assessment in remote and high mountain lakes of Gilgit Baltistan, Pakistan - Maryem Mehboob; Rachid Dris; Bruno Tassin; Johnny Gasperi; Muhammad Usman Khan; Riffat N. Malik (Chemosphere, 2024)

Improving green hydrogen production: Microwave-assisted synthesis of diverse Ni-based nanocatalysts on Al2O3 for thermochemical water splitting - Salma Samidin; Wan Nor Roslam Wan Isahak; Khairul Naim Ahmad; N. Asikin Mijan; Muhammad Rahimi Yusop; Alinda Samsuri; G. Abdulkareem-Alsultan; Mohd Ambar Yarmo (Fuel, 2024)

A review of heavy metals pollution in riverine sediment from various Asian and European countries: Distribution, sources, and environmental risk - Maria Zeb; Kifayatullah Khan; Muhammad Younas; Abida Farooqi; Xianghui Cao; Yasar N. Kavil; Saeed Saad Alelyani; Mohammed M. Alkasbi; Abdullah G. Al-Sehemi (Marine Pollution Bulletin, 2024)

Mangrove (Avicennia marina) Conservation Contributed to a Higher Carbon Sequestration Rate at Protected Sites Compared to Overgrazed Mangrove Forests - Amal S. Dajam; Amr E. Keshta; Ahmed A. Bindajam; Rahma N. Al-Qthanin; Muhammad Arshad; Ebrahem M. Eid (Journal of Soil Science and Plant Nutrition, 2024)

Correction: Spatial distribution and health risks assessment of heavy metals in e-waste dumping sites from Pakistan - Muhammad Zaffar Hashmi; Sohaib Khan; Yasar N. Kavil; Saeed Saad Alelyani; Abdullah G. Al Sehemi; Ahmad Hasnain; Sidra Shakil; Shuhong Wang; Zulkifl Ahmed (Environmental Geochemistry and Health, 2024)

Using deep learning to automate the detection of bird scaring lines on fishing vessels - Debaditya Acharya; Muhammad Saqib; Carlie Devine; Candice Untiedt; L. Richard Little; Dadong Wang; Geoffrey N. Tuck (Biological Conservation, 2024)

Maleated Hydroxyethyl Cellulose for the Efficient Removal of Cd(II) Ions from an Aqueous Solution: Isothermal, Kinetic and Regeneration Studies - Fatima Khan; Abu Bakar Siddique; Muhammad Imran Irfan; Muhammad Naeem ul Hassan; Muhammad Sher; Hassan A. Alhazmi; Abdulrahman N. Qramish; Hatem M. A. Amin; Rahman Qadir; Azhar Abbas (Water, Air, & Soil Pollution, 2024)

Chemical analogue based drug design for cancer treatment targeting PI3K: integrating machine learning and molecular modeling - Mohammed A. Bazuhair; Anwar A. Alghamdi; Othman Baothman; Muhammad Afzal; Sami I. Alzarea; Faisal Imam; Ehssan Moglad; Hisham N. Altayb (Molecular Diversity, 2024)

Spatial distribution and health risks assessment of heavy metals in e-waste dumping sites from Pakistan - Muhammad Zaffar Hashmi; Sohaib Khan; Yasar N. Kavil; Saeed Saad Alelyani; Abdullah G. Al Sehemi; Ahmad Hasnain; Sidra Shakil; Shuhong Wang; Zulkifl Ahmed (Environmental Geochemistry and Health, 2024)

Monitoring activity in Mount Melbourne, Antarctica, by multi-temporal SAR interferometry based on the ICOPS algorithm - Wahyu L. Hakim; Raisa N. Sakina; Muhammad F. Fadhillah; Seulki Lee; Sungjae Park; Hyun-Cheol Kim; Chang-Wook Lee (Geosciences Journal, 2024)

Soil nitrogen dynamics affected by coffee (coffea arabica) canopy and fertilizer management in coffee-based agroforestry - Syahrul Kurniawan; R Muhammad Yusuf Adi Pujo Nugroho; Reni Ustiatik; Istika Nita; Gabryna Auliya Nugroho; Cahyo Prayogo; Christopher W. N. Anderson (Agroforestry Systems, 2024)
Nutrient management in coffee-based agroforestry systems plays a critical role in soil nitrogen (N) cycling, but has not been well documented. The objective of this study was to evaluate the effect of coffee canopy management and fertilization on soil N dynamics. This study used a randomized complete block design (2 × 3 × 2) with four replications. There were three factors: 1) coffee canopy management (T1: Pruned, T2: Unpruned), 2) fertilizer type (O: Organic, I: Inorganic; M: 50% Organic + 50% Inorganic), and 3) fertilizer dose (D1: low, D2: medium, D3: high). Soil N dynamic indicators (i.e., total N, ammonium (NH 4 + ), nitrate (NO 3 − ), net N-NH 4 + , net N-NO 3 − , soil microbial biomass N) were measured at two soil sampling depths (0–20 cm and 20–40 cm). Results showed that pruning increased soil total N and microbial biomass N (MBN) by 10–56% relative to unpruned coffee trees. In contrast, the unpruned coffee canopy had 15–345% higher NH 4 + , NO 3 − , net N-NH 4 + , net N-NO 3 − , and microbial biomass N concentration than pruned coffee. Mixed fertilizer application increased NO 3 − and net N-NH 4 + accumulation by 5–15% relative to inorganic and organic fertilizers. In addition, medium to high dose fertilization led to a 19–86% higher net N-NO 3 − concentration and microbial biomass N as compared to low dose fertilization. The treatment of no pruning and mixed fertilizer at low to medium doses was the optimal management strategy to maintain soil available N, while pruning combined with organic fertilizer has the potential to improve soil total N and MBN.

In-situ groundwater remediation of contaminant mixture of As(III), Cr(VI), and sulfanilamide via electrochemical degradation/transformation using pyrite - Jong-Gook Kim; Stephanie Sarrouf; Muhammad Fahad Ehsan; Akram N. Alshawabkeh; Kitae Baek (Journal of Hazardous Materials, 2024)

Insect meal in aquafeeds: A sustainable path to enhanced mucosal immunity in fish - S.M. Majharul Islam; Muhammad A.B. Siddik; Mette Sørensen; Monica F. Brinchmann; Kim D. Thompson; David S. Francis; Ioannis N. Vatsos (Fish & Shellfish Immunology, 2024)

Integrated phycoremediation and modified PES-PVP fiber with biosynthesized n-AgO from Arabidopsis thaliana extract for remediating shrimp wastewater - M. Abdulsalam; H. C. Man; A. F. Abdullah; M. M. A. Karim; M. I. Aida Isma; M. M. Muhammad; N. A. Muhadi (International Journal of Environmental Science and Technology, 2024)

Population exposure to emerging perfluoroalkyl acids (PFAAs) via drinking water resources: Application of multivariate statistics and risk assessment models - Kifayatullah Khan; Muhammad Younas; Jafar Ali; Noor Samad Shah; Yasar N. Kavil; Mohammed A. Assiri; Xianghui Cao; Hassan Sher; Afsheen Maryam; Yunqiao Zhou; Muhammad Yaseen; Li Xu (Marine Pollution Bulletin, 2024)

Metasurfaces: Shaping the future of photonics - Nikolay L. Kazanskiy; Svetlana N. Khonina; Muhammad A. Butt (Science Bulletin, 2024)

Mucosal barrier status in Atlantic salmon fed rapeseed oil and Schizochytrium oil partly or fully replacing fish oil through winter depression - SM Majharul Islam; Florence Perera Willora; Mette Sørensen; Golam Rbbani; Muhammad A.B. Siddik; Kyla Zatti; Shruti Gupta; Ian Carr; Ester Santigosa; Monica F. Brinchmann; Kim D. Thompson; Ioannis N. Vatsos (Fish & Shellfish Immunology, 2024)

Recent Advances of carbon Pathways for Sustainable Environment development - K.S. Aryamol; Kuppusamy Kanagaraj; Senthilkumar Nangan; Jozef T. Haponiuk; Manunya Okhawilai; Saravanan Pandiaraj; Muhammad Bilal Hanif; Abdullah N. Alodhayb; Sabu Thomas; Natesan Thirumalaivasan; Sreeraj Gopi (Environmental Research, 2024)

Non-lamellar lyotropic liquid crystalline nanoparticles as nanocarriers for enhanced drug encapsulation of atorvastatin calcium and proanthocyanidins - Mardhiah Maslizan; Muhammad Salahuddin Haris; Mokrish Ajat; Siti Nurul Ain Md Jamil; Shah Christirani Azhar; N. Idayu Zahid; Intan Diana Mat Azmi (Chemistry and Physics of Lipids, 2024)

Effects of supplementation of different selenium sources on lipid profile, selenium, and vitamin E concentration of yolk - N. I. M. Hemly; N. N. Zainudin; A. I. Muhammad; T. C. Loh; A. A. Samsudin (Tropical Animal Health and Production, 2024)

Recent advances in microbial-assisted degradation and remediation of xenobiotic contaminants; challenges and future prospects - A.K. Priya; M. Muruganandam; Anuj Kumar; N. Senthilkumar; Mohd Shkir; Bidhan Pandit; Muhammad Imran; Chander Prakash; Mohd Ubaidullah (Journal of Water Process Engineering, 2024)

The osteogenic potential of seaweed: A systematic review and meta-analysis - Suriani Saleng; Faqi Nurdiansyah Hendra; Muhammad Ruslin; Tymour Forouzanfar; Marco N. Helder (Algal Research, 2024)

Removal of cesium and strontium ions with enhanced solid-liquid separation by combined ion exchange and BaSO4 co-precipitation - Oguzhan Kivan; Muhammad Yusuf; David Harbottle; Timothy N. Hunter (Journal of Water Process Engineering, 2024)

Teat morphology across five buffalo breeds: a multi-country collaborative study - Carlo Boselli; Angela Costa; Massimo De Marchi; Muhammad A. Zia; Muhammad Q. Shahid; Nasim Ahmad; Ivan Fasulkov; Manol Karadaev; Yordanka Ilieva; Pencho Penchev; Fatemeh Derisavi; Mohammad Nikookar; et al. (Tropical Animal Health and Production, 2024)

Lupin and Lima Beans Diminish Potatoes’ N and P Uptake, Uptake Efficiency and Use Efficiency - Mustafa A. Haile; Nancy N. Karanja; Shadrack O. Nyawade; Harun I. Gitari; Gladys Cheruto; Lukelysia Nyawira; Muhammad Ali Raza; Solomon Kamau (Potato Research, 2024)

Enhancing systematic tolerance in Bermuda grass (Cynodon dactylon L.) through amplified alkB gene expression and bacterial-driven hydrocarbon degradation - Sehrish Iqbal; Ume Ummara; Sibgha Noreen; Muhammad Salim Akhter; Farrukh Jaleel; Shazia Jabeen; Nargis Naz; Abdul Wahid; Modhi O. Alotaibi; Mudawi M. Nour; Rahmah N. Al-Qthanin; Muhammad Aqeel (Environmental Science and Pollution Research, 2024)

Development of a culturally targeted chatbot to inform living kidney donor candidates of African ancestry about APOL1 genetic testing: a mixed methods study - Elisa J. Gordon; Jessica Gacki-Smith; Matthew J. Gooden; Preeya Waite; Rochell Yacat; Zenab R. Abubakari; Debra Duquette; Akansha Agrawal; John Friedewald; Sarah K. Savage; Matthew Cooper; Alexander Gilbert; et al. (Journal of Community Genetics, 2024)
Clinical chatbots are increasingly used to help integrate genetic testing into clinical contexts, but no chatbot exists for A polipoprotein L1 ( APOL1 ) genetic testing of living kidney donor (LKD) candidates of African ancestry. Our study aimed to culturally adapt and assess perceptions of the Gia® chatbot to help integrate APOL1 testing into LKD evaluation. Ten focus groups and post-focus group surveys were conducted with 54 LKDs, community members, and kidney transplant recipients of African ancestry. Data were analyzed through thematic analysis and descriptive statistics. Key themes about making Gia culturally targeted included ensuring: (1) transparency by providing Black LKDs’ testimonials, explaining patient privacy and confidentiality protections, and explaining how genetic testing can help LKD evaluation; (2) content is informative by educating Black LKDs about APOL1 testing instead of aiming to convince them to undergo testing, presenting statistics, and describing how genetic discrimination is legally prevented; and (3) content avoids stigma about living donation in the Black community. Most agreed Gia was neutral and unbiased (82%), trustworthy (82%), and words, phrases, and expressions were familiar to the intended audience (85%). Our culturally adapted APOL1 Gia chatbot was well regarded. Future research should assess how this chatbot could supplement provider discussion prior to genetic testing to scale APOL1 counseling and testing for LKD candidate clinical evaluation.

Molecular characterization of genes involved in tolerance of cadmium in Triticum aestivum (L.) under Cd stress - Asima Rasheed; Arwa Abdulkreem AL-Huqail; Baber Ali; Suliman Mohammed Suliman Alghanem; Asad Ali Shah; Farrukh Azeem; Muhammad Rizwan; Rahmah N. Al-Qthanin; Fathia A. Soudy (Journal of Hazardous Materials, 2024)

Effect of fire and post-fire management on soil microbial communities in a lower subtropical forest ecosystem after a mountain fire - Mengmeng Yang; Xuan Luo; Ying Cai; Brian N. Mwangi; Muhammad Sadiq Khan; Fasih Ullah Haider; Wanxuan Huang; Xianli Cheng; Zefan Yang; Hongen Zhou; Shizhong Liu; Qianmei Zhang; et al. (Journal of Environmental Management, 2024)

Theoretical and experimental explored tailored hybrid H+/O2– ions conduction: Bridged for high performance fuel cell and water electrolysis - Zuhra Tayyab; Sajid Rauf; Muhammad Bilal Hanif; Hafiz Imran Ahmad Qazi; Naveed Mushtaq; Martin Motola; Sining Yun; Chen Xia; Dmitry A. Medvedev; Muhammad Imran Asghar; Abdullah N. Alodhayb; Arshad Hussain; et al. (Chemical Engineering Journal, 2024)

Cancer Stem Cells Niche Regulation Within the Tumor Microenvironment - Zainab Siddiqui; Zaffar Equbal; Naoshad Muhammad; Darksha Usmani; Satya N. Sankhwar; S. Nishat Fatima Rizvi; Abdul Naeem (Current Tissue Microenvironment Reports, 2024)

Mitigating chromium toxicity in rice (Oryza sativa L.) via ABA and 6-BAP: Unveiling synergistic benefits on morphophysiological traits and ASA-GSH cycle - Khairiah Mubarak Alwutayd; Suliman Mohammed Suliman Alghanem; Rahaf Alwutayd; Sameera A. Alghamdi; Nadiyah M. Alabdallah; Rahmah N. Al-Qthanin; Wajiha Sarfraz; Noreen Khalid; Nayab Naeem; Baber Ali; Muhammad Hamzah Saleem; Sadia Javed; et al. (Science of The Total Environment, 2024)

Synchrotron speciation of umbilical cord mercury and selenium after environmental exposure in Niigata - Monica Weng; Natalia V. Dolgova; Linda I. Vogt; Muhammad Qureshi; Dimosthenis Sokaras; Thomas Kroll; Hisashi Saitō; John L. O’Donoghue; Gene E. Watson; Gary J. Myers; Tomoko Sekikawa; Ingrid J. Pickering; et al. (NeuroToxicology, 2024)

Use of iron-bearing waste materials in laundry wastewater treatment - Yara Arbid; Muhammad Usman; N. Tan Luong; Baptiste Mathon; Bruno Cedat; Jean-François Boily; Khalil Hanna (Journal of Water Process Engineering, 2024)

Recent outbreak of Marburg virus; a global health concern and future perspective - Usama Mujahid; Muhammad Ahmad; Attiqa Mujahid; Edward Narayan; Saif Ur Rehman; Hafiz M. N. Iqbal; Ishtiaq Ahmed (European Journal of Clinical Microbiology & Infectious Diseases, 2024)

Contrasting genetic and morphological differentiation among geographical lineages of a stenotopic miniature rasborine, Boraras maculatus , in P eninsular M alaysia - Yi Qing Fam; Jamsari Amirul Firdaus Jamaluddin; Abdullah Halim Muhammad‐Rasul; Mohd Lokman Ilham‐Norhakim; Nik Fadzly N. Rosely; Sébastien Lavoué (Journal of Fish Biology, 2024)
The variability in the stenotopic miniature rasborine Boraras maculatus (Cypriniformes: Danionidae: Rasborinae) across acidic‐water habitats of Peninsular Malaysia (PM) was investigated using two molecular markers (the mitochondrial cytochrome c oxidase subunit I [COI] gene and the nuclear rhodopsin gene), as well as morphological evidence. Molecular phylogenetic analyses revealed differentiation among populations of B. maculatus in PM with the distinction of four allopatric lineages. Each of them was recognized as a putative species by automatic species delimitation methods. These lineages diverged from each other between 7.4 and 1.9 million years ago. A principal component analysis (PCA) was conducted to examine the multivariate variation in 11 morphometric measurements among three of these lineages. PCA results showed a significant overlap in morphological characteristics among these lineages. Additionally, a photograph‐based machine learning approach failed to fully differentiate these lineages, suggesting limited morphological differentiation. B. maculatus represents a case of morphological stasis in a stenotopic miniature species. Strong habitat preference, coupled with long‐term habitat fragmentation, may explain why each lineage of B. maculatus has a restricted distribution and did not disperse to other regions within and outside of PM, despite ample possibilities when the Sunda shelf was emerged and drained by large paleodrainages for most of the past 7 million years. The conservation status of B. maculatus and its peat swamp habitats are discussed, and it is concluded that peat swamps comprise several evolutionary units. Each of these units is considered a conservation unit and deserves appropriate protection.

Advancements in technology and innovation for sustainable agriculture: Understanding and mitigating greenhouse gas emissions from agricultural soils - Muhammad Qayyum; Yanping Zhang; Mansi Wang; Yuyuan Yu; Shijie Li; Wasim Ahmad; Saleh N. Maodaa; Shaban R.M. Sayed; Jiawei Gan (Journal of Environmental Management, 2023)

New insights on designing the next-generation materials for electrochemical synthesis of reactive oxidative species towards efficient and scalable water treatment: A review and perspectives - Amir Taqieddin; Stephanie Sarrouf; Muhammad Fahad Ehsan; Akram N. Alshawabkeh (Journal of Environmental Chemical Engineering, 2023)

Impact of ultrasonication on the contents, profiles and biofunctional properties of free and bound phenolics from white desert truffle (Tirmania nivea) and its protein fractions - Muhammad H. Alu'datt; Carole C. Tranchant; Mohammad N. Alhamad; Taha Rababah; Doa'a Al-U'datt; Sana Gammoh; Mohammad Alrosan; Sharifa Alkandari; Roa'a Zghoul (Food Research International, 2023)

Recent advances in microalgae, insects, and cultured meat as sustainable alternative protein sources - Nayab Fatima; Mohammad Naushad Emambux; Amin N. Olaimat; Alexandros Ch Stratakos; Asad Nawaz; Agung Wahyono; Khalid Gul; Jiyong Park; Hafiz Muhammad Shahbaz (Food and Humanity, 2023)

Socio-economic impacts of solar energy technologies for sustainable green energy: a review - Ahmed N. Abdalla; Wang Jing; Muhammad Shahzad Nazir; Mingxin Jiang; Hao Tao (Environment, Development and Sustainability, 2023)

Morphometric and genetic variations of three grouper species (genus Epinephelus) from the northern region of Aceh province, Indonesia - Nur Fadli; Adrian Damora; Zainal Abidin Muchlisin; Mutia Ramadhaniaty; Nanda Muhammad Razi; Sri Riska Rahayu; Edison D. Macusi; Ahasan Habib; Mohd N. Siti-Azizah (Zoologischer Anzeiger, 2023)

Renewable hydrogen production via biological and thermochemical routes: Nanomaterials, economic analysis and challenges - Fazil Qureshi; Mohammad Yusuf; Muhammad Tahir; Moinul Haq; Montaha Mohamed Ibrahim Mohamed; Hesam Kamyab; Hong-Ha T. Nguyen; Dai-Viet N. Vo; Hussameldin Ibrahim (Process Safety and Environmental Protection, 2023)

Nanosheet arrays of iron oxide for enhanced ammonia synthesis via electrochemical nitrogen reduction for prospective algal membrane bioreactors - Muhammad Adnan Younis; Saira Manzoor; Amjad Ali; Fazal Haq; Tariq Aziz; Mehwish Kiran; Arshad Farid; Mohamed E. El Sayed; Mohammad N. Murshed; Zeinhom M. El-Bahy; Muhammad Saeed Akhtar (Chemosphere, 2023)

Heavy metals in five commonly consumed fish species from River Swat, Pakistan, and their implications for human health using multiple risk assessment approaches - Kifayatullah Khan; Maria Zeb; Muhammad Younas; Hafiz Muhammad Adeel Sharif; Muhammad Yaseen; Abdullah G. Al-Sehemi; Yasar N. Kavil; Noor Samad Shah; Xianghui Cao; Afsheen Maryam; Muhammad Qasim (Marine Pollution Bulletin, 2023)

Synergistic Removal of Methylene Blue and Disinfection of Escherichia coli by Photocatalytic Tungsten-Loaded Titanium Dioxide-Coated Fiberglass - Saepurahman; Antudrika Sheryna Mandala; Muhammad Eka Prastya; Keiichi N. Ishihara; Mohd Azmuddin Abdullah; Andreas (Water, Air, & Soil Pollution, 2023)

Novel sol–gel synthesis of Mo-doped ZnO-NPs for photo-catalytic waste water treatment using the RhB dye as a model pollutant - Muhammad Sohaib; Tahir Iqbal; Sumera Afsheen; M. B. Tahir; Arslan Masood; Muhammad Rafique; K. N. Riaz; M. A. Sayed; A. F. Abd El-Rehim; Atif Mossad Ali (Environment, Development and Sustainability, 2023)

Enhancing the stability of shale in water-based fluid with polyethylene glycol/nanosilica composite grafted with sodium dodecyl sulfate - Shafeeg Omer Blkoor; Muhammad Noorul Anam Bin Mohd Norddin; Issham Ismail; Jeffrey Onuoma Oseh; Saeed S. Basaleh; Abdul Rahim Bin Risal; Mohd Firdaus Bin Sariman; Eugene N. Ngouangna (Arabian Journal of Geosciences, 2023)

Effects of n-3 HUFA-enriched Artemia on growth, biochemical response, skeletal morphology and stress resistance of Asian sea bass (Lates calcarifer) larvae reared at high temperature - Hung Duc Pham; Muhammad A.B. Siddik; Md. Arifur Rahman; Lan Tuyet Huynh; Ashfaqun Nahar; Ioannis N. Vatsos (Aquaculture, 2023)

Arachidonic acid modulates the cellular energetics of human pluripotent stem cells and protects the embryoid bodies from embryotoxicity effects in vitro - Muhammad Nihad; Utsav Sen; Debajit Chaudhury; Undurti N. Das; Sudheer Shenoy P; Bipasha Bose (Reproductive Toxicology, 2023)

Corrigendum to “Priming of adipose-derived stem cells with curcumin prior to cryopreservation preserves their functional potency: Towards an ‘Off-the-shelf’ therapy for burns” [Cryobiology 110 (2023) 69–78] - Maryam Azam; Hafiz Ghufran; Saba Tasneem; Azra Mehmood; Kausar Malik; Muhammad Amin Yousaf; Moazzam N. Tarar; Shehla Javed Akram; Sheikh Riazuddin (Cryobiology, 2023)

Cold and Drought Stresses in Wheat: A Global Meta-analysis of 21st Century - Irsa Ejaz; Xiaoyu Pu; Muhammad Asad Naseer; Yves N.’Dri Bohoussou; Ying Liu; Muhammad Farooq; Jingting Zhang; Yinghua Zhang; Zhimin Wang; Zhencai Sun (Journal of Plant Growth Regulation, 2023)

Graphene derivatives-based electrodes for the electrochemical determination of carbamate pesticides in food products: A review - Muhammad Saqib; Anna N. Solomonenko; Jiří Barek; Elena V. Dorozhko; Elena I. Korotkova; Shojaa A. Aljasar (Analytica Chimica Acta, 2023)

Transforming Lignin Biomass to Value: Interplay Between Ligninolytic Enzymes and Lignocellulose Depolymerization - Namra Ahmad; Shakira Aslam; Nazim Hussain; Muhammad Bilal; Hafiz M. N. Iqbal (BioEnergy Research, 2023)
Lignin is the main constituent of lignocellulosic biomasses, which have a significant untapped ability to replace ecologically unfavorable and non-renewable fossil fuels. The lignin is broken down by ligninolytic bacteria, which also use a peripheral pathway to transform heterogeneous lignin derivatives into central intermediates like protocatechuate or catechol. By undergoing ring cleavage through the -ketoadipate pathway, these intermediates become metabolites by producing acetyl-CoA for internal product biosynthesis, including the creation of triacylglycerols and polyhydroxyalkanoates. Expanding our understanding of ligninolytic microbial communities, strains, and enzymes through bioprospecting can help us better understand the metabolism of aromatics. The most viable idea for sustainable development is the valorization of lignin into biopolymers as well as other high-value goods. This process is now being used to generate a variety of biopolymers, including polyesters, epoxies, phenol resins, poly (lactic acids), poly hydroxyl alkanoates, and polyurethanes. Furthermore, lignin recalcitrance remained a possible barrier to efficient lignin valorization, prompting several efforts to design high-efficiency bioprocesses to produce specific polymer types as well as other important bioproducts. Graphical Abstract

In-situ hydrogen peroxide formation and persulfate activation over banana peel-derived biochar cathode for electrochemical water treatment in a flow reactor - Jong-Gook Kim; Stephanie Sarrouf; Muhammad Fahad Ehsan; Kitae Baek; Akram N. Alshawabkeh (Chemosphere, 2023)

Enhanced Degradation of Acid Orange 52 Using a Polyextremophilic Ascomycete in Stirred Tank Bioreactor - Qandeel Laraib; Maryam Shafique; Muhammad Ali Versiani; Khitab Gul; Uroosa Ejaz; Haji Muhammad; Sehar Afshan Naz; Drauzio E. N. Rangel; Alene Alder-Rangel; Kousar Yasmeen; Nusrat Jabeen; Jing Liu; et al. (Water, Air, & Soil Pollution, 2023)

Modelling compound flooding: a case study from Jakarta, Indonesia - William G. Bennett; Harshinie Karunarathna; Yunqing Xuan; Muhammad S. B. Kusuma; Mohammad Farid; Arno A. Kuntoro; Harkunti P. Rahayu; Benedictus Kombaitan; Deni Septiadi; Tri N. A. Kesuma; Richard Haigh; Dilanthi Amaratunga (Natural Hazards, 2023)
The paper investigates compound flooding from waves, sea surge and river flow in northern Jakarta, Indonesia, which is a global hotspot of flooding, by combining process-based coastal and river models. The coastal hydrodynamic modelling of Jakarta Bay in Indonesia shows that coastal storms can lead to a substantial increase in sea water level due to wind and wave setup in the nearshore areas, including Muara Angke river inlet. The compound flood hazard from a range of flood scenarios was simulated and analysed. The results reveal that low-lying areas around the river inlet are prone to flooding even during regular, low-intensity storm events, while rarer storms caused extensive floods. Floods were not caused by direct overwashing of sea defences but by overspill of the banks of the river inlet due to high sea water level caused by wind set up, wave setup, and sea surge obstructing the drainage of the river and elevating its water level during storms. We also found that the sea level rise combined with rapid land subsidence will inundate the existing coastal flood defences during storms in future. The majority of the city will be below mean sea level by 2100. The overflow of existing coastal defences will lead to extensive flooding in northern, western, and eastern Jakarta unless the defences are upgraded to keep up with future sea level rise.

Balancing nitrate acquisition strategies in symbiotic legumes - Zainab Rahmat; Muhammad N. Sohail; Francine Perrine-Walker; Brent N. Kaiser (Planta, 2023)
Main conclusion Legumes manage both symbiotic (indirect) and non-symbiotic (direct) nitrogen acquisition pathways. Understanding and optimising the direct pathway for nitrate uptake will support greater legume growth and seed yields. Abstract Legumes have multiple pathways to acquire reduced nitrogen to grow and set seed. Apart from the symbiotic N 2 -fixation pathway involving soil-borne rhizobia bacteria, the acquisition of nitrate and ammonia from the soil can also be an important secondary nitrogen source to meet plant N demand. The balance in N delivery between symbiotic N (indirect) and inorganic N uptake (direct) remains less clear over the growing cycle and with the type of legume under cultivation. In fertile, pH balanced agricultural soils, NO 3 − is often the predominant form of reduced N available to crop plants and will be a major contributor to whole plant N supply if provided at sufficient levels. The transport processes for NO 3 − uptake into legume root cells and its transport between root and shoot tissues involves both high and low-affinity transport systems called HATS and LATS, respectively. These proteins are regulated by external NO 3 − availability and by the N status of the cell. Other proteins also play a role in NO 3 − transport, including the voltage dependent chloride/nitrate channel family (CLC) and the S-type anion channels of the SLAC/SLAH family. CLC’s are linked to NO 3 − transport across the tonoplast of vacuoles and the SLAC/SLAH’s with NO 3 − efflux across the plasma membrane and out of the cell. An important step in managing the N requirements of a plant are the mechanisms involved in root N uptake and the subsequent cellular distribution within the plant. In this review, we will present the current knowledge of these proteins and what is understood on how they function in key model legumes ( Lotus japonicus, Medicago truncatula and Glycine sp.). The review will examine their regulation and role in N signalling, discuss how post-translational modification affects NO 3 − transport in roots and aerial tissues and its translocation to vegetative tissues and storage/remobilization in reproductive tissues. Lastly, we will present how NO 3 − influences the autoregulation of nodulation and nitrogen fixation and its role in mitigating salt and other abiotic stresses.

In vitro-produced equine blastocysts exhibit dispersed ICM cell allocation - Muhammad Umair; Anthony N Claes; Verônica F da Cunha Scheeren; Mabel M Beitsma; Silvia Colleoni; Cesare Galli; Giovanna Lazzari; Marta de Ruijter-Villani; Tom A Stout (Journal of Equine Veterinary Science, 2023)

Highly Ecofriendly Inorganic Pesticide Based on TiO2 Incorporated with Nano-Carbon Composites for Phytophthora palmivora Fungus Disinfection - Muhammad Nurdin; Icheu Dini Widia Sari; Mardhatillah Mardhatillah; N. Herdianto; Dwiprayogo Wibowo; Maulidiyah Maulidiyah; Musadar Mappasomba; Ansharullah Ansharullah; Catherina Bijang (Indian Journal of Microbiology, 2023)

Review of microplastics in the indoor environment: Distribution, human exposure and potential health impacts - M. Dewika; Kalaimani Markandan; N Ahmad Irfan; Muhammad Amirul Aizat Mohd Abdah; J.Nor Ruwaida; Y.Y. Sara; Mohammad Khalid (Chemosphere, 2023)

Municipal solid waste treatment for bioenergy and resource production: Potential technologies, techno-economic-environmental aspects and implications of membrane-based recovery - Naila Amin; Muhammad Aslam; Zakir khan; Muhammad Yasin; Shakhawat Hossain; Muhammad Kashif Shahid; Abrar Inayat; Ahmed Samir; Rizwan Ahmad; Mohammad N. Murshed; Muhammad Shahzad Khurram; Mohamed E. El Sayed; et al. (Chemosphere, 2023)

Corrigendum to “An empirical investigation of resource curse hypothesis for cobalt” [Resour. Pol. (2022) 102843] - Veli Yilanci; N. Ceren Turkmen; Muhammad Ibrahim Shah (Resources Policy, 2023)

Effects of supplementing organic- and inorganic-based selenium with vitamin E on intestinal histomorphology, caecal bacterial proliferation, and short-chain fatty acid profile in layer hens - N.N. Zainudin; N.I.M. Hemly; A.I. Muhammad; N. Nayan; A.A. Samsudin (Tropical Animal Health and Production, 2023)

Development of a universal landslide hazard potential model for mudrock slopes: fuzzy logic and molecular-level modelling approaches - Habib ur-Rehman; Sahel N. Abduljauwad; Muhammad Naeemuddin (Natural Hazards, 2023)

Barriers to completion of cascade genetic testing: how can we improve the uptake of testing for hereditary breast and ovarian cancer syndrome? - Ryan Matthew Kahn; Muhammad Danyal Ahsan; Eloise Chapman-Davis; Kevin Holcomb; Roni Nitecki; Jose Alejandro Rauh-Hain; Rana Khan Fowlkes; Francesca Tubito; Maira Pires; Paul J Christos; Kaitlyn Tkachuk; Hannah Krinsky; et al. (Familial Cancer, 2023)

Cryptic biodiversity inhabiting coral reef sponges - Anita M. George; Dave Abdo; Muhammad Azmi Abdul Wahab; Merrick Ekins; John N. A. Hooper; Steve Whalan (Marine Ecology, 2023)
Sponges host a wide range of cryptic biodiversity both internally and externally. This study quantified the biodiversity inhabiting, or associated with, three morphologically distinct coral reef sponges. Coelocarteria singaporensis , Coscinoderma mathewsi and Ircinia microconulosa were collected from fringing reefs at Orpheus Island, central Great Barrier Reef, across monsoonal seasons (wet and dry) and diurnal periods (morning, afternoon and night for C . singaporensis ) to quantify Sponge Associated Biota (SAB). A total of 8489 SAB was sorted from 77 sponges. Twenty‐six taxa, across 3 kingdoms and 12 phyla were recorded. Sponge‐associated biota was dominated by Mollusca in all three sponge hosts (range ~ 46%–50%) but taxa were found from a number of other phyla including, Arthropoda, Annelida, Echinodermata, Cnidaria, Foraminifera and Nemertea. There was no effect of season on abundances of SAB within the three species of sponge, but there was a significant effect associated with sponge host species, driven by a higher number of SAB in C . singaporensis and I . microconulosa . The diurnal patterns of SAB within C . singaporensis showed consistent abundances of mobile invertebrate groups with molluscs, echinoderms and arthropods dominating these samples. This study also highlights the ecological role and contribution of SAB in the reef ecosystems.

Morphometric and genetic variations of four dominant species of snappers (Lutjanidae) harvested from the Northern Coast of Aceh waters, Indonesia - Sri Riska Rahayu; Zainal A. Muchlisin; Nur Fadli; Nanda Muhammad Razi; Mutia Ramadhaniaty; Luvi Syafrida Handayani; Siti Maulida; Firman M. Nur; Nurlaili Nurlaili; Moh N. Siti-Azizah (Zoologischer Anzeiger, 2023)

Evaluation of quality and protein structure of natural water kefir-fermented quinoa protein concentrates - Mohammad Alrosan; Thuan-Chew Tan; Azhar Mat Easa; Sana Gammoh; Muhammad H. Alu'datt; Ghada Mohamed Aleid; Mohammad N. Alhamad; Sofyan Maghaydah (Food Chemistry, 2023)

Priming of adipose-derived stem cells with curcumin prior to cryopreservation preserves their functional potency: Towards an ‘Off-the-shelf’ therapy for burns - Maryam Azam; Hafiz Ghufran; Saba Tasneem; Azra Mehmood; Kausar Malik; Muhammad Amin Yousaf; Moazzam N. Tarar; Shehla Javed Akram; Sheikh Riazuddin (Cryobiology, 2023)

A sustainable utilization of aquaculture wastewater for the production of commercially important tilapia fish and plants (mint and chickpea) in improved integrated aqua-agriculture system - A. Muhammad Alameen; K. Nanthini Devi; S. Dinesh Kumar; S. Gunabal; N. Krishnaveni; A. Gowthami; S. Sinduja; J. Roopavathy; P. Santhanam; G. Roseline Jebapriya; M. Saranya; A. Aravinth; et al. (Bioresource Technology Reports, 2023)

A comparative study of different types of the inversion algorithms for the reservoir characterization of Mehar Block, Pakistan - Nizam Ud Din; Muhammad Kashif; Jamil Khan; Zaheer Hussain; Jose N. Mendez; Wasif Saeed (Arabian Journal of Geosciences, 2023)

Characterization and Bioactivities of Sequentially-Prepared Sea Cucumber Ethanolic Extracts and Protein Hydrolysates - Ariyanti S. Dewi; Mei Arumia; Dohan A. Samodro; Nurrahmi D. Fajarningsih; Gintung Patantis; Muhammad Nursid; Irmanida Batubara; Yusro N. Fawzya (Journal of Aquatic Food Product Technology, 2023)

Advanced experimental techniques for the sensitive detection of a toxic bisphenol A using UiO-66-NDC/GO-based electrochemical sensor - T.S. Sunil Kumar Naik; Simranjeet Singh; Pavithra N; Radhika Varshney; Basavaraju Uppara; Joginder Singh; Nadeem A. Khan; Lakhveer Singh; Muhammad Zulqarnain Arshad; Praveen C. Ramamurthy (Chemosphere, 2023)

Paddy rice methane emissions across Monsoon Asia - Zutao Ouyang; Robert B. Jackson; Gavin McNicol; Etienne Fluet-Chouinard; Benjamin R.K. Runkle; Dario Papale; Sara H. Knox; Sarah Cooley; Kyle B. Delwiche; Sarah Feron; Jeremy Andrew Irvin; Avni Malhotra; et al. (Remote Sensing of Environment, 2023)

Reduced Fine API Agglomeration After Dry Coating for Enhanced Blend Uniformity and Processability of Low Drug Loaded Blends - Sangah S. Kim; Chelsea Castillo; Muhammad Sayedahmed; Rajesh N. Davé (Pharmaceutical Research, 2022)

The COVID-19 impact on air condition usage: a shift towards residential energy saving - Muhammad Saidu Aliero; Muhammad Fermi Pasha; Adel N. Toosi; Imran Ghani (Environmental Science and Pollution Research, 2022)

Effect of Different Solubilization pH Values on the Functional Properties of Protein Spirulina platensis Isolated Through Acidic Precipitation - N. A. Kamaruding; N. A. Muhammad Daud; N. Ismail; S. Shaharuddin (Journal of Aquatic Food Product Technology, 2022)

Nutritional Profiling of Wild (Pangasius pangasius) and Farmed (Pangasius hypophthalmus) Pangasius Catfish with Implications to Human Health - Suprakash Chakma; Md. Arifur Rahman; Muhammad A. B. Siddik; Md. Sazedul Hoque; SM Majharul Islam; Ioannis N. Vatsos (Fishes, 2022)
This study analyzed and compared the nutritional profiles of wild (Pangasius pangasius) and farmed (Pangasius hypophthalmus) pangasius catfish collected from the various sources of river and culture ponds in Bangladesh. The results indicated that the wild pangasius catfish had a significantly (p

Neurotoxic effects of environmental contaminants—measurements, mechanistic insight, and environmental relevance - Nadia Afsheen; Sadia Rafique; Hamza Rafeeq; Kanwal Irshad; Asim Hussain; Zille Huma; Vineet Kumar; Muhammad Bilal; Lotfi Aleya; Hafiz M. N. Iqbal (Environmental Science and Pollution Research, 2022)

SARS-COV-2/COVID-19: scenario, epidemiology, adaptive mutations, and environmental factors - Asma Asghar; Hafiz Muhammad Imran; Naheed Bano; Sadia Maalik; Sajida Mushtaq; Asim Hussain; Sunita Varjani; Lotfi Aleya; Hafiz M. N. Iqbal; Muhammad Bilal (Environmental Science and Pollution Research, 2022)

Robust bioinspired surfaces and their exploitation for petroleum hydrocarbon remediation - Nisar Ali; Essoh Lionnelle Gyllye; Chuansong Duanmu; Yong Yang; Adnan Khan; Farman Ali; Muhammad Bilal; Hafiz M. N. Iqbal (Environmental Science and Pollution Research, 2022)

Comparison of single-trait and multi-trait genomic predictions on agronomic and disease resistance traits in spring wheat - Kassa Semagn; José Crossa; Jaime Cuevas; Muhammad Iqbal; Izabela Ciechanowska; Maria Antonia Henriquez; Harpinder Randhawa; Brian L. Beres; Reem Aboukhaddour; Brent D. McCallum; Anita L. Brûlé-Babel; Amidou N’Diaye; et al. (Theoretical and Applied Genetics, 2022)

Nanotechnology-based controlled release of sustainable fertilizers. A review - Bilal Beig; Muhammad Bilal Khan Niazi; Farooq Sher; Zaib Jahan; Umer Shahzad Malik; Mohammad Daud Khan; Juliana Heloisa Pinê Américo-Pinheiro; Dai-Viet N. Vo (Environmental Chemistry Letters, 2022)
The rising population is increasing food demand, yet actual crop production is limited by the poor efficiency of classical fertilizers. In particular, only about 40–60% of fertilizer nitrogen, 15–20% of phosphorus and 50–60% of potassium are used by crop plants, the rest ending polluting the environment. Nanofertilizers are promising alternatives. Here, we review plant nutrients, synthesis of zinc oxide nanoparticles, encapsulation of nanoparticles in fertilizers, and effect on plants.

Novel strategies and advancement in reducing heavy metals from the contaminated environment - Quratulain Maqsood; Nazim Hussain; Mehvish Mumtaz; Muhammad Bilal; Hafiz M. N. Iqbal (Archives of Microbiology, 2022)

Insight into soil nitrogen and phosphorus availability and agricultural sustainability by plant growth-promoting rhizobacteria - Qingwei Zeng; Xiaolei Ding; Jiangchuan Wang; Xuejiao Han; Hafiz M. N. Iqbal; Muhammad Bilal (Environmental Science and Pollution Research, 2022)

A review on proliferation of artificial intelligence in wind energy forecasting and instrumentation management - Lijun Zhao; Muhammad Shahzad Nazir; Hafiz M. Jamsheed Nazir; Ahmed N. Abdalla (Environmental Science and Pollution Research, 2022)

Therapeutic potential of herbal medicine for the management of hyperlipidemia: latest updates - Abdur Rauf; Muhammad Akram; Hina Anwar; Muhammad Daniyal; Naveed Munir; Sami Bawazeer; Saud Bawazeer; Maksim Rebezov; Abdelhakim Bouyahya; Mohammad Ali Shariati; Muthu Thiruvengadam; Orynzhamal Sarsembenova; et al. (Environmental Science and Pollution Research, 2022)

Ionic liquids for the inhibition of gas hydrates. A review - Ihtisham Ul Haq; Ali Qasim; Bhajan Lal; Dzulkarnain B. Zaini; Khor Siak Foo; Muhammad Mubashir; Kuan Shiong Khoo; Dai-Viet N. Vo; Eric Leroy; Pau Loke Show (Environmental Chemistry Letters, 2022)

Gums-based engineered bio-nanostructures for greening the 21st-century biotechnological settings - Muhammad Bilal; Hira Munir; Muhammad Imran Khan; Mohsin Khurshid; Tahir Rasheed; Komal Rizwan; Marcelo Franco; Hafiz M. N. Iqbal (Critical Reviews in Food Science and Nutrition, 2022)

Chemical composition of three Malaysian Horsfieldia essential oils - Wan Mohd Nuzul Hakimi Wan Salleh; Natasa Mohd Shakri; Shamsul Khamis; William N. Setzer; Muhammad Helmi Nadri (Natural Product Research, 2022)

Microalgae binary culture for higher biomass production, nutrients recycling, and efficient harvesting: a review - Md. Asraful Alam; Chun Wan; Dang Thuan Tran; M. Mofijur; Shams Forruque Ahmed; Muhammad Aamer Mehmood; Feroz Shaik; Dai-Viet N. Vo; Jingliang Xu (Environmental Chemistry Letters, 2022)

Production and antioxidant activity of secondary metabolites in Hassawi rice (Oryza sativa L.) cell suspension under salicylic acid, yeast extract, and pectin elicitation - Hossam S. El-Beltagi; Heba I. Mohamed; Mohammed I. Aldaej; Jameel M. Al-Khayri; Adel A. Rezk; Muneera Q. Al-Mssallem; Muhammad N. Sattar; Khaled M. A. Ramadan (In Vitro Cellular & Developmental Biology - Plant, 2022)

Genome-based prediction of agronomic traits in spring wheat under conventional and organic management systems - Kassa Semagn; Muhammad Iqbal; José Crossa; Diego Jarquin; Reka Howard; Hua Chen; Darcy H. Bemister; Brian L. Beres; Harpinder Randhawa; Amidou N’Diaye; Curtis Pozniak; Dean Spaner (Theoretical and Applied Genetics, 2022)

Nano-structured dynamic Schiff base cues as robust self-healing polymers for biomedical and tissue engineering applications: a review - Umer Shahzad Malik; Muhammad Bilal Khan Niazi; Zaib Jahan; Mazhar Iqbal Zafar; Dai-Viet N. Vo; Farooq Sher (Environmental Chemistry Letters, 2022)
Polymer materials are vulnerable to damages, failures, and degradations, making them economically unreliable. Self-healing polymers, on the other hand, are multifunctional materials with superior properties of autonomic recovery from physical damages. These materials are suitable for biomedical and tissue engineering in terms of cost and durability. Schiff base linkages-based polymer materials are one of the robust techniques owing to their simple self-healing mechanism. These are dynamic reversible covalent bonds, easy to fabricate at mild conditions, and can self-reintegrate after network disruption at physiological conditions making them distinguished. Here we review self-healing polymer materials based on Schiff base bonds. We discuss the Schiff base bond formation between polymeric networks, which explains the self-healing phenomenon. These bonds have induced 100% recovery in optimal cases.

Dendritic Cell–Targeted Therapies to Treat Neurological Disorders - Asim Hussain; Hamza Rafeeq; Nimra Munir; Zara Jabeen; Nadia Afsheen; Khalil ur Rehman; Muhammad Bilal; Hafiz M. N. Iqbal (Molecular Neurobiology, 2022)

Separation and remediation of environmental pollutants using metal–organic framework-based tailored materials - Walter Dzumbira; Nisar Ali; Chuansong Duanmu; Yong Yang; Adnan Khan; Farman Ali; Muhammad Bilal; Lotfi Aleya; Hafiz M. N. Iqbal (Environmental Science and Pollution Research, 2022)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Bio-purification of sugar industry wastewater and production of high-value industrial products with a zero-waste concept - Muhammad Zohaib Nawaz; Muhammad Bilal; Arslan Tariq; Hafiz M. N. Iqbal; Huda Ahmed Alghamdi; Hairong Cheng (Critical Reviews in Food Science and Nutrition, 2021)

Physical mapping of QTL associated with agronomic and end-use quality traits in spring wheat under conventional and organic management systems - Kassa Semagn; Muhammad Iqbal; Hua Chen; Enid Perez-Lara; Darcy H. Bemister; Rongrong Xiang; Jun Zou; Muhammad Asif; Atif Kamran; Amidou N’Diaye; Harpinder Randhawa; Brian L. Beres; et al. (Theoretical and Applied Genetics, 2021)

Ecotoxicological Assessment and Environmental Risk of the Insecticide Chlorpyrifos for Aquatic Neotropical Indicators - Márjori Brenda Leite Marques; Isabella Alves Brunetti; Camila Aparecida Faleiros; Claudinei da Cruz; Hafiz M. N. Iqbal; Muhammad Bilal; Juliana Heloisa Pinê Américo-Pinheiro (Water, Air, & Soil Pollution, 2021)

Revisiting the Role of Biologically Active Natural and Synthetic Compounds as an Intervention to Treat Injured Nerves - Natália Melo Souza; Mateus Figueiredo Gonçalves; Luiz Fernando Romanholo Ferreira; Muhammad Bilal; Hafiz M. N. Iqbal; Renato Nery Soriano (Molecular Neurobiology, 2021)

Nanotechnology-based immunotherapies to combat cancer metastasis - Yuping Zhao; Muhammad Bilal; Maimoona Qindeel; Muhammad Imran Khan; Kuldeep Dhama; Hafiz M. N. Iqbal (Molecular Biology Reports, 2021)

Correction to: Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Production of a broad spectrum streptothricin like antibiotic from halotolerant Streptomyces fimbriatus isolate G1 associated with marine sediments - Neelma Ashraf; Andreas Bechthold; Munir A. Anwar; Muhammad A. Ghauri; Muhammad S. Anjum; Ali N. Khan; Kalsoom Akhtar; Shazia Khaliq (Folia Microbiologica, 2021)

A multidisciplinary approach applied to paleokarst zones of the Tahe area, China: compositional scheme and reservoir quality—case study - Jose N. Mendez; Qiang Jin; Muhammad Kashif; Hugo Govea; Freddy Marin (Arabian Journal of Geosciences, 2021)

Assessment of early physiological and biochemical responses in chia (Salvia hispanica L.) sprouts under salt stress - Mahmoud E. Younis; Muhammad Rizwan; Shaimaa M. N. Tourky (Acta Physiologiae Plantarum, 2021)

Catalytic transformation of Brassica nigra oil into biodiesel using in-house engineered green catalyst: Development and characterization - Ushna Fatima; Farooq Ahmad; Muhammad Ramzan; Saba Aziz; Muhammad Tariq; Hafiz M. N. Iqbal; Muhammad Imran (Clean Technologies and Environmental Policy, 2021)

Spatio-temporal variability of chlorophyll- a in response to coastal upwelling and mesoscale eddies in the South Eastern Arabian Sea - Muhammad Shafeeque; A. N. Balchand; Phiros Shah; Grinson George; Smitha B. R.; Eldho Varghese; Ajith K. Joseph; Shubha Sathyendranath; Trevor Platt (International Journal of Remote Sensing, 2021)

Synergistic Effect of Urease and Nitrification Inhibitors in the Reduction of Ammonia Volatilization - Asim Hussain; Nazish Jahan; Zara Jabeen; Khalil Ur Rehman; Hamza Rafeeq; Muhammad Bilal; Hafiz M. N. Iqbal (Water, Air, & Soil Pollution, 2021)

Seasonal Dynamics of Microbial Contamination and Antibiotic Resistance in the Water at the Tietê Ecological Park, Brazil - Darlan Storto; Luana Barbosa Carvalho Nara; Dora Inés Kozusny-Andreani; Luiz Sergio Vanzela; Cleber Fernando Menegasso Mansano; Muhammad Bilal; Hafiz M. N. Iqbal; Juliana Heloisa Pinê Américo-Pinheiro (Water, Air, & Soil Pollution, 2021)

A new virus of the family Tombusviridae infecting sugarcane - Muhammad N. Tahir; Stephen Bolus; Samuel C. Grinstead; Sharon A. McFarlane; Dimitre Mollov (Archives of Virology, 2021)

Yarrowia lipolytica as an emerging biotechnological chassis for functional sugars biosynthesis - Muhammad Bilal; Shuo Xu; Hafiz M. N. Iqbal; Hairong Cheng (Critical Reviews in Food Science and Nutrition, 2021)

Microbial exopolysaccharide-based nano-carriers with unique multi-functionalities for biomedical sectors - Muhammad Asgher; Sarmad Ahmad Qamar; Hafiz M. N. Iqbal (Biologia, 2021)

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Phenotypic characterisation and linkage mapping of domestication syndrome traits in yellow lupin (Lupinus luteus L.) - Muhammad Munir Iqbal; William Erskine; Jens D. Berger; Matthew N. Nelson (Theoretical and Applied Genetics, 2020)
The transformation of wild plants into domesticated crops usually modifies a common set of characters referred to as ‘domestication syndrome’ traits such as the loss of pod shattering/seed dehiscence, loss of seed dormancy, reduced anti-nutritional compounds and changes in growth habit, phenology, flower and seed colour. Understanding the genetic control of domestication syndrome traits facilitates the efficient transfer of useful traits from wild progenitors into crops through crossing and selection. Domesticated forms of yellow lupin ( Lupinus luteus L.) possess many domestication syndrome traits, while their genetic control remains a mystery. This study aimed to reveal the genetic control of yellow lupin domestication traits. This involved phenotypic characterisation of those traits, defining the genomic regions controlling domestication traits on a linkage map and performing a comparative genomic analysis of yellow lupin with its better-understood relatives, narrow-leafed lupin ( L. angustifolius L.) and white lupin ( L. albus L.). We phenotyped an F 9 recombinant inbred line (RIL) population of a wide cross between Wodjil (domesticated) × P28213 (wild). Vernalisation responsiveness, alkaloid content, flower and seed colour in yellow lupin were each found to be controlled by single loci on linkage groups YL-21, YL-06, YL-03 and YL-38, respectively. Aligning the genomes of yellow with narrow-leafed lupin and white lupin revealed well-conserved synteny between these sister species (76% and 71%, respectively). This genomic comparison revealed that one of the key domestication traits, vernalisation-responsive flowering, mapped to a region of conserved synteny with the vernalisation-responsive flowering time Ku locus of narrow-leafed lupin, which has previously been shown to be controlled by an FT homologue. In contrast, the loci controlling alkaloid content were each found at non-syntenic regions among the three species. This provides a first glimpse into the molecular control of flowering time in yellow lupin and demonstrates both the power and the limitation of synteny as a tool for gene discovery in lupins.

Genetic analyses of native Fusarium head blight resistance in two spring wheat populations identifies QTL near the B1, Ppd-D1, Rht-1, Vrn-1, Fhb1, Fhb2, and Fhb5 loci - Dinushika Thambugala; Anita L. Brûlé-Babel; Barbara A. Blackwell; George Fedak; Adam J. Foster; Dan MacEachern; Jeannie Gilbert; Maria Antonia Henriquez; Richard A. Martin; Brent D. McCallum; Dean Spaner; Muhammad Iqbal; et al. (Theoretical and Applied Genetics, 2020)

Rabies virus infection in mice up-regulates B7-H1 via epigenetic modifications - Comfort E. Ojedapo; Aliyu Muhammad; Grace S. N. Kia; Musa M. Abarshi; Maryam Abdulazeez; Joy Cecilia Atawodi; Jacob K. P. Kwaga (VirusDisease, 2020)

Environmental impacts and risk factors of renewable energy paradigm—a review - Muhammad Shahzad Nazir; Ziad M. Ali; Muhammad Bilal; Hafiz M. Sohail; Hafiz M. N. Iqbal (Environmental Science and Pollution Research, 2020)

Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

State-of-the-art strategies and applied perspectives of enzyme biocatalysis in food sector — current status and future trends - Muhammad Bilal; Hafiz M. N. Iqbal (Critical Reviews in Food Science and Nutrition, 2020)

Induction of Rabies Virus Infection in Mice Brain may Up and Down Regulate Type II Interferon gamma via epigenetic modifications - Maryam Abdulazeez; Grace S. N. Kia; Musa M. Abarshi; Aliyu Muhammad; Comfort E. Ojedapo; Joy Cecilia Atawodi; David Dantong; Jacob K. P. Kwaga (Metabolic Brain Disease, 2020)

Assessment of denitrification potential for coastal and inland sites using groundwater and soil analysis: the multivariate approach - Muntaka Dahiru; Nor Kartini Abu Bakar; Ismail Yus off; Kah Hin Low; Muhammad N. Mohd (Environmental Monitoring and Assessment, 2020)

Tachykinin-1 receptor antagonism suppresses substance-P- and compound 48/80-induced mast cell activation from rat mast cells expressing functional mas-related GPCR B3 - Muhammad N. A. Sahid; Shuang Liu; Masaki Mogi; Kazutaka Maeyama (Inflammation Research, 2020)

Photocatalytic Degradation of Congo Red Dye from Aqueous Environment Using Cobalt Ferrite Nanostructures: Development, Characterization, and Photocatalytic Performance - Nisar Ali; Amir Said; Farman Ali; Fazal Raziq; Zarshad Ali; Muhammad Bilal; Laurence Reinert; Tasleem Begum; Hafiz M. N. Iqbal (Water, Air, & Soil Pollution, 2020)

Assessing Drug Release from Manipulated Abuse Deterrent Formulations - Xin Feng; Ahmed Zidan; Nahid S. Kamal; Xiaoming Xu; Dajun Sun; Ross Walenga; Heather Boyce; Celia N. Cruz; Muhammad Ashraf (AAPS PharmSciTech, 2020)

Modification of acidic and textural properties of a sulphated zirconia catalyst for efficient conversion of high-density polyethylene into liquid fuel - Muhammad N. Almustapha; Muhammad Farooq; Misbahu L. Mohammed; Muhammad Farhan; Muhammad Imran; John M. Andresen (Environmental Science and Pollution Research, 2020)

Phytotoxic analysis of coastal medicinal plants and quantification of phenolic compounds using HPLC - Muhammad Qasim; Yoshiharu Fujii; Muhammad Zaheer Ahmed; Irfan Aziz; Kazuo N. Watanabe; M. Ajmal Khan (Plant Biosystems, 2019)

Pore size distribution and reservoir characterization: evaluation for the Eocene beach-bar sequence, Dongying Depression, China - Muhammad Aleem Zahid; Dong Chunmei; Alexandra N. Golab; Chengyan Lin; Xianguo Zhang; Xinmin Ge; Wu Songtao; Muhammad Jawad Munawar; Cunfei Ma; Lydia Knuefing (Arabian Journal of Geosciences, 2019)

Bioethanol Mill Wastewater Purification by Combination of Coagulation-Flocculation and Microbial Treatment of Trametes versicolor INACC F200 - Ajeng Arum Sari; Tony Hadibarata; Ummu Hanifah; Ahmad Randy; Feni Amriani; Puspa Dewi N. Lotulung; Hasbi Yasin; Asep Saefumillah; Muhammad Ilyas (Water, Air, & Soil Pollution, 2019)

Bambara groundnut: an exemplar underutilised legume for resilience under climate change - Sean Mayes; Wai Kuan Ho; Hui Hui Chai; Xiuqing Gao; Aloyce C. Kundy; Kumbirai I. Mateva; Muhammad Zahrulakmal; Mohd Khairul Izwan Mohd Hahiree; Presidor Kendabie; Luis C. S. Licea; Festo Massawe; Tafadzwanashe Mabhaudhi; et al. (Planta, 2019)

Climatology of the spring Red Sea Trough - Muhammad N. Baseer; Adel M. Awad; Mansour Almazroui (International Journal of Climatology, 2019)
The spring Sudan low and its Red Sea Trough (RST) were detected objectively using sea level pressure data obtained from a National Center for Environmental Prediction/National Center for Atmospheric Research reanalysis dataset spanning the period from 1955 to 2014. The climatology of the detected lows suggested that the Sudan low was active for approximately 69.5% of the spring and that approximately 56.2% of this time the Sudan low developed into the RST. Furthermore, three main genesis regions of the RST, which generated 95.25% of the RST, were identified over Sudan, South Sudan and the Red Sea, approximately 61.76% of which was over South Sudan. In addition, three main outermost areas of the RST, which received 94.1% of the RST, were specified to the west, east and north of the Red Sea, approximately 54.88% of which was in the eastern region. Synoptically, the orientations of the detected RST around the Red Sea are strongly influenced by the Siberian and Azores high systems. The RST is directed along the western side of the Red Sea if the Siberian high extends westward and the Azores high shrinks westward, whereas the RST is oriented to the east if the Siberian high shrinks eastward and the Azores high extends eastward. The RST extends directly northward if the Siberian and Azores high systems withdraw eastward and westward, respectively. These results also demonstrate that the core position and strength of the upper maximum winds play an important role in the generation of RST. The selected case studies have confirmed the synoptic climate results and indicate that the Sudan low will not develop into RST when the northern region has been affected by a high‐pressure system and the core of the upper maximum wind is located over the northern Arabian Peninsula.

Predicting Down syndrome and neural tube defects using basic risk factors - Momina T. Khattak; Eko Supriyanto; Muhammad N. Aman; Rania H. Al-Ashwal (Medical & Biological Engineering & Computing, 2019)

A systematic review on black pepper (Piper nigrum L.): from folk uses to pharmacological applications - Heerasing Takooree; Muhammad Z. Aumeeruddy; Kannan R.R. Rengasamy; Katharigatta N. Venugopala; Rajesh Jeewon; Gokhan Zengin; Mohamad F. Mahomoodally (Critical Reviews in Food Science and Nutrition, 2019)

Periodic vicissitudes of different concentrations of a developed prototype killed S. aureus mastitis vaccine on immune modulators, mediators and immunoglobulins in cows - Idris Umar Hambali; Faez Firdaus Jesse Bin Abdullah; K. R. Bhutto; M. L. Mohd Azmi; A. H. Wahid; Z. Zakaria; M. N. Odhah; M. Arsalan; N. A. Muhammad; M. N. Jefri (Tropical Animal Health and Production, 2019)

Phosphonium-based hydrophobic ionic liquids with fluorous anions for biodiesel production from waste cooking oil - Z. Ullah; M. A. Bustam; Z. Man; A. S. Khan; A. Sarwono; N. Muhammad; M. Farooq; S. N. Shah; P. Ahmad; S. Haider (International Journal of Environmental Science and Technology, 2019)

Synthesis of 4-formyl pyridinium propylthioacetate stabilized silver nanoparticles and their application in chemosensing of 6-aminopenicillanic acid (APA) - A. Anwar; M. R. Shah; S. P. Muhammad; K. Ali; N. A. Khan (International Journal of Environmental Science and Technology, 2019)

Occurrence, types, properties and interactions of phenolic compounds with other food constituents in oil-bearing plants - Muhammad H. Alu'datt; Taha Rababah; Mohammad N. Alhamad; Ghaid J. Al-Rabadi; Carole C. Tranchant; Ali Almajwal; Stan Kubow; Inteaz Alli (Critical Reviews in Food Science and Nutrition, 2018)

Metabolic engineering pathways for rare sugars biosynthesis, physiological functionalities, and applications—a review - Muhammad Bilal; Hafiz M. N. Iqbal; Hongbo Hu; Wei Wang; Xuehong Zhang (Critical Reviews in Food Science and Nutrition, 2018)

Coupled physicochemical and bacterial reduction mechanisms for passive remediation of sulfate- and metal-rich acid mine drainage - S. N. Muhammad; F. M. Kusin; Z. Madzin (International Journal of Environmental Science and Technology, 2018)

Characterization of Huanglongbing disease associated with acid lime (Citrus aurantifolia Swingle) in Oman - Ahmed Al Fahdi; Alghaliya Al-Mamari; Muhammad S. Shahid; Sajeewa S. N. Maharachchikumbura; Claudine M. Carvalho; Simon L. Elliot; Abdullah M. Al-Sadi (Journal of Plant Pathology, 2018)

In vitro preconditioning of insulin-producing cells with growth factors improves their survival and ability to release insulin - Muhammad Sohail Anjum; Azra Mehmood; Faiza Mahmood; Muhammad Ali; Moazzam Nazir Tarrar; Shaheen N. Khan; Sheikh Riazuddin (Journal of Biosciences, 2018)

Factors influencing corrosion of metal pipes in soils - Muhammad Wasim; Shahrukh Shoaib; N. M. Mubarak; Inamuddin; Abdullah M. Asiri (Environmental Chemistry Letters, 2018)

The 2014 Earthquake Model of the Middle East: seismogenic sources - Laurentiu Danciu; Karin Şeşetyan; Mine Demircioglu; Levent Gülen; Mehdi Zare; Roberto Basili; Ata Elias; Shota Adamia; Nino Tsereteli; Hilal Yalçın; Murat Utkucu; Muhammad Asif Khan; et al. (Bulletin of Earthquake Engineering, 2018)

Identification of pedilanthus leaf curl virus and associated betasatellite infecting turnip in Pakistan - Samrah Munir; Muhammad Khurshid; Hira Kanwal; Mujahid Hussain; Muhammad N. Sattar; Irfan Ali; Atiq-ur Rehman; Zafar Iqbal (Journal of Plant Pathology, 2018)

Isolation of Bacillus cereus from botanical soil and subsequent biodegradation of waste engine oil - S. Bhurgri; F. N. Talpur; S. M. Nizamani; H. I. Afridi; M. A. Surhio; Muhammad Raza Shah; C. W. Bong (International Journal of Environmental Science and Technology, 2018)

Identification, Characterization and Expression Profiles of Dof Transcription Factors in Pineapple (Ananas comosus L) - Syed Muhammad Azam; Yanhui Liu; Zia Ur Rahman; Hina Ali; Cheng Yan; Lulu Wang; S. V. G. N. Priyadarshani; Binyan Hu; Xinyu Huang; Junjie Xiong; Yuan Qin (Tropical Plant Biology, 2018)

Development and validation of a loop-mediated isothermal amplification assay for the detection of Mycoplasma bovis in mastitic milk - Aqeela Ashraf; Muhammad Imran; Tahir Yaqub; Muhammad Tayyab; Wasim Shehzad; Claro N. Mingala; Yung-Fu Chang (Folia Microbiologica, 2018)

Impact of grazing on soil, vegetation and ewe production performances in a semi-arid rangeland - Muhammad Islam; Abdul Razzaq; Shamim Gul; Sarfraz Ahmad; Taj Muhammad; Sawsan Hassan; Barbara Rischkowsky; M. N. M. Ibrahim; Mounir Louhaichi (Journal of Mountain Science, 2018)

Spatio-Temporal Patterns in the Coral Reef Communities of the Spermonde Archipelago, 2012–2014, II: Fish Assemblages Display Structured Variation Related to Benthic Condition - Jeremiah G. Plass-Johnson; Mirta Teichberg; Vanessa N. Bednarz; Astrid Gärdes; Jasmin P. Heiden; Muhammad Lukman; Sara Miñarro; Hauke Kegler; Laura Weiand; Christian Wild; Hauke Reuter; Sebastian C. A. Ferse (Frontiers in Marine Science, 2018)

Spatio-Temporal Patterns in Coral Reef Communities of the Spermonde Archipelago, 2012–2014, I: Comprehensive Reef Monitoring of Water and Benthic Indicators Reflect Changes in Reef Health - Mirta Teichberg; Christian Wild; Vanessa N. Bednarz; Hauke F. Kegler; Muhammad Lukman; Astrid A. Gärdes; Jasmin P. Heiden; Laura Weiand; Nur Abu; Andriani Nasir; Sara Miñarro; Sebastian C. A. Ferse; et al. (Frontiers in Marine Science, 2018)

Barcode index numbers expedite quarantine inspections and aid the interception of nonindigenous mealybugs (Pseudococcidae) - Jing-Mei Ren; Muhammad Ashfaq; Xu-Nan Hu; Jun Ma; Fan Liang; Paul D. N. Hebert; Li Lin; Jean François Germain; Muhammad Z. Ahmed (Biological Invasions, 2018)

Toxicological Assessment and UV/TiO2-Based Induced Degradation Profile of Reactive Black 5 Dye - Muhammad Bilal; Tahir Rasheed; Hafiz M. N. Iqbal; Hongbo Hu; Wei Wang; Xuehong Zhang (Environmental Management, 2018)

Application of Optical Coherence Tomography Freeze-Drying Microscopy for Designing Lyophilization Process and Its Impact on Process Efficiency and Product Quality - Maxwell Korang-Yeboah; Charudharshini Srinivasan; Akhtar Siddiqui; David Awotwe-Otoo; Celia N. Cruz; Ashraf Muhammad (AAPS PharmSciTech, 2018)

Comparison of Seasonal Cycles of Phytoplankton Chlorophyll, Aerosols, Winds and Sea-Surface Temperature off Somalia - Muhammad Shafeeque; Shubha Sathyendranath; Grinson George; Alungal N. Balchand; Trevor Platt (Frontiers in Marine Science, 2017)

Advances and future directions of biochar characterization methods and applications - Avanthi Deshani Igalavithana; Sanchita Mandal; Nabeel Khan Niazi; Meththika Vithanage; Sanjai J. Parikh; Fungai N. D. Mukome; Muhammad Rizwan; Patryk Oleszczuk; Mohammad Al-Wabel; Nanthi Bolan; Daniel C. W. Tsang; Ki-Hyun Kim; et al. (Critical Reviews in Environmental Science and Technology, 2017)

Expression Profiles of Wuschel-Related Homeobox Gene Family in Pineapple (Ananas comosus L) - Zia ur Rahman; Syed Muhammad Azam; Yanhui Liu; Cheng Yan; Hina Ali; Lihua Zhao; Piaojuan Chen; Li Yi; S. V. G. N. Priyadarshani; Qin Yuan (Tropical Plant Biology, 2017)

Regenerative Stem Cell Therapy Optimization via Tissue Engineering in Heart Failure with Reduced Ejection Fraction - Mehmet Alkan; Raef Madanieh; Niel N. Shah; Muhammad U. Dogar; Parin N. Shah; Sameera Ishtiaq; Constantine E. Kosmas; Timothy J. Vittorio (Cardiovascular Engineering and Technology, 2017)

Engineering Pseudomonas for phenazine biosynthesis, regulation, and biotechnological applications: a review - Muhammad Bilal; Shuqi Guo; Hafiz M. N. Iqbal; Hongbo Hu; Wei Wang; Xuehong Zhang (World Journal of Microbiology and Biotechnology, 2017)

Effective Bioremediation of Endocrine-Disrupting Phthalate Esters, Mediated by Bacillus Strains - Muhammad Ali Surhio; Farah N. Talpur; Shafi M. Nizamani; Marvi Kanwal Talpur; Farah Amin; Abid Ali Khaskheli; Shazia Bhurgri; Hassan Imran Afridi; Shafiq Ur Rahman (Water, Air, & Soil Pollution, 2017)

Synthesis, crystal structure, anti-HIV, and antiproliferative activity of new pyrazolylthiazole derivatives - Murtaza Madni; Shahid Hameed; Muhammad N. Ahmed; Muhammad N. Tahir; Najim A. Al-Masoudi; Christophe Pannecouque (Medicinal Chemistry Research, 2017)

Molecular and biologic characterization of a phytoplasma associated with Brassica campestris phyllody disease in Punjab province, Pakistan - Jam Nazeer Ahmad; Samina J. N. Ahmad; Muhammad Aslam; Muhammad Aijaz Ahmad; Nicoletta Contaldo; Samanta Paltrinieri; Assunta Bertaccini (European Journal of Plant Pathology, 2017)

Reaction Mechanism and Degradation Pathway of Rhodamine 6G by Photocatalytic Treatment - Tahir Rasheed; Muhammad Bilal; Hafiz M. N. Iqbal; Hongbo Hu; Xuehong Zhang (Water, Air, & Soil Pollution, 2017)

Leaching of phthalate esters from different drinking stuffs and their subsequent biodegradation - Muhammad Ali Surhio; Farah N. Talpur; Shafi M. Nizamani; Marvi Kanwal Talpur; Hassan Imran Afridi; Abid Ali Khaskheli; Shazia Bhurgri; Junaid Ali Surhio (Environmental Science and Pollution Research, 2017)

Application of spectral decomposition for the detection of fluvial sand reservoirs, Indus Basin, SW Pakistan - Muhammad N. Tayyab; Shazia Asim (Geosciences Journal, 2017)

Enzyme-based solutions for textile processing and dye contaminant biodegradation—a review - Shahzad Ali Shahid Chatha; Muhammad Asgher; Hafiz M. N. Iqbal (Environmental Science and Pollution Research, 2017)

Molecular characterization of previously elusive badnaviruses associated with symptomatic cacao in the New World - Nomatter Chingandu; Muhammad Zia-ur-rehman; Thyail N. Sreenivasan; Surendra Surujdeo-Maharaj; Pathmanathan Umaharan; Osman A. Gutierrez; Judith K. Brown (Archives of Virology, 2017)

Characterization and complete genome sequence of a panicovirus from Bermuda grass by high-throughput sequencing - Muhammad N. Tahir; Ben Lockhart; Samuel Grinstead; Dimitre Mollov (Archives of Virology, 2017)

Bio-based degradation of emerging endocrine-disrupting and dye-based pollutants using cross-linked enzyme aggregates - Muhammad Bilal; Muhammad Asgher; Hafiz M. N. Iqbal; Hongbo Hu; Xuehong Zhang (Environmental Science and Pollution Research, 2017)

Arabidopsis AtNAP functions as a negative regulator via repression of AREB1 in salt stress response - Hye-Yeon Seok; Dong-Hyuk Woo; Linh Vu Nguyen; Huong T. Tran; Vaishali N. Tarte; Syed Muhammad Muntazir Mehdi; Sun-Young Lee; Yong-Hwan Moon (Planta, 2017)

Rutin Attenuates Carfilzomib-Induced Cardiotoxicity Through Inhibition of NF-κB, Hypertrophic Gene Expression and Oxidative Stress - Faisal Imam; Naif O. Al-Harbi; Mohammed M. Al-Harbia; Hesham M. Korashy; Mushtaq Ahmad Ansari; Mohamed M. Sayed-Ahmed; Mahmoud N. Nagi; Muzaffar Iqbal; Md. Khalid Anwer; Imran Kazmi; Muhammad Afzal; Saleh Bahashwan (Cardiovascular Toxicology, 2017)

Investigation of novel LPS-induced differentially expressed long non-coding RNAs in endothelial cells - Krishna K. Singh; Pratiek N. Matkar; Shoaib Muhammad; Adrian Quan; Vijay Gupta; Hwee Teoh; Mohammed Al-Omran; Subodh Verma (Molecular and Cellular Biochemistry, 2016)

Molecular Analysis of Drought Tolerance in Guava Based on In Vitro PEG Evaluation - Eman Abouzaid; El-Sayed N. El-Sayed; El-Sayed A. Mohamed; Muhammad Youssef (Tropical Plant Biology, 2016)

The role of new eudesmane-type sesquiterpenoid and known eudesmane derivatives from the red alga Laurencia obtusa as potential antifungal–antitumour agents - Walied M. Alarif; Khalid O. Al-Footy; Muhammad Sulaiman Zubair; Mohamed Halid PH; Mohamed A. Ghandourah; Salim A. Basaif; Sultan S. Al-Lihaibi; Seif-Eldin N. Ayyad; Farid A. Badria (Natural Product Research, 2016)

A review of steroids from Sarcophyton species - Muhammad Sulaiman Zubair; Khalid O. Al-Footy; Seif-Eldin N. Ayyad; Sultan S. Al-Lihaibi; Walied M. Alarif (Natural Product Research, 2016)

Diazoxide preconditioning of endothelial progenitor cells from streptozotocin-induced type 1 diabetic rats improves their ability to repair diabetic cardiomyopathy - Muhammad Ali; Azra Mehmood; Muhammad Sohail Anjum; Moazzam Nazir Tarrar; Shaheen N. Khan; Sheikh Riazuddin (Molecular and Cellular Biochemistry, 2015)

Correlation of Arsenic Levels in Smokeless Tobacco Products and Biological Samples of Oral Cancer Patients and Control Consumers - Sadaf S. Arain; Tasneem G. Kazi; Hassan I. Afridi; Farah N. Talpur; Atif G. Kazi; Kapil D. Brahman; Naeemullah; Abdul H. Panhwar; Muhammad A. Kamboh (Biological Trace Element Research, 2015)

Neuroprotective effect from stem bark extracts of Knema laurina against H 2 O 2 - and Aβ 1–42 -induced cell death in human SH-SY5Y cells - Norsharina Ismail; Muhammad Nadeem Akhtar; Maznah Ismail; Seema Zareen; Syed Adnan Ali Shah; Nordin Hj Lajis; Saiful N. Tajuddin (Natural Product Research, 2015)

Knowledge, attitude, and practice of Indonesian farmers regarding the use of personal protective equipment against pesticide exposure - Maria G. C. Yuantari; Cornelis A. M. Van Gestel; Nico M. Van Straalen; Budi Widianarko; Henna R. Sunoko; Muhammad N. Shobib (Environmental Monitoring and Assessment, 2015)

Evaluation of PAH contamination in soil treated with solid by-products from shale pyrolysis - Jaqueline Nicolini; Muhammad Y. Khan; M. Matsui; Lílian C. Côcco; Carlos I. Yamamoto; Wilson A. Lopes; Jailson B. de Andrade; Clenio N. Pillon; Gregorio G. Carbajal Arizaga; Antonio S. Mangrich (Environmental Monitoring and Assessment, 2015)

In contrast to many other mammals, cetaceans have relatively small hippocampi that appear to lack adult neurogenesis - Nina Patzke; Muhammad A. Spocter; Karl Æ. Karlsson; Mads F. Bertelsen; Mark Haagensen; Richard Chawana; Sonja Streicher; Consolate Kaswera; Emmanuel Gilissen; Abdulaziz N. Alagaili; Osama B. Mohammed; Roger L. Reep; et al. (Brain Structure and Function, 2015)

History and Origin of Russet Burbank (Netted Gem) a Sport of Burbank - Paul C. Bethke; Atef M. K. Nassar; Stan Kubow; Yves N. Leclerc; Xiu-Qing Li; Muhammad Haroon; Teresa Molen; John Bamberg; Max Martin; Danielle J. Donnelly (American Journal of Potato Research, 2014)

Spectroscopic Investigation, Effect of Solvent Polarity and Fluorescence Quenching of a New D-π-A Type Chalcone Derivative - Mehboobali Pannipara; Abdullah M. Asiri; Khalid A. Alamry; Muhammad N Arshad; Samy A. El-Daly (Journal of Fluorescence, 2014)

Fluoroquinolones: novel class of gastrointestinal dietary lipid digestion and absorption inhibitors - Yusuf M. Al-Hiari; Violet N. Kasabri; Ashok K. Shakya; Muhammad H. Alzweiri; Fatma U. Afifi; Yasser K. Bustanji; Ihab M. Al-Masri (Medicinal Chemistry Research, 2014)

Isolation of Peripheral Blood Mononuclear Cells Using Glycerol Density Gradient - I. A. Aimola; H. M. Inuwa; A. J. Nok; A. I. Mamman; N. Habila; A. Muhammad; U. S. Ndidi; B. Ignatius; P. L. Jande; R. Oghor; L. C. Isaac; N. B. Afolabi-Balogun (Cell Biochemistry and Biophysics, 2014)

Changes in extreme temperature and precipitation in the Arab region: long‐term trends and variability related to ENSO and NAO - M. G. Donat; T. C. Peterson; M. Brunet; A. D. King; M. Almazroui; R. K. Kolli; Djamel Boucherf; Anwar Yousuf Al‐Mulla; Abdourahman Youssouf Nour; Ahmed Attia Aly; Tamer Ali Ali Nada; Muhammad M. Semawi; et al. (International Journal of Climatology, 2014)
A workshop was held in Casablanca, Morocco, in March 2012, to enhance knowledge of climate extremes and their changes in the Arab region. This workshop initiated intensive data compilation activities of daily observational weather station data from the Arab region. After conducting careful control processes to ensure the quality and homogeneity of the data, climate indices for extreme temperatures and precipitation were calculated. This study examines the temporal changes in climate extremes in the Arab region with regard to long‐term trends and natural variability related to ENSO and NAO . We find consistent warming trends since the middle of the 20th Century across the region. This is evident in the increased frequencies of warm days and warm nights, higher extreme temperature values, fewer cold days and cold nights and shorter cold spell durations. The warming trends seem to be particularly strong since the early 1970s. Changes in precipitation are generally less consistent and characterised by a higher spatial and temporal variability; the trends are generally less significant. However, in the western part of the Arab region, there is a tendency towards wetter conditions. In contrast, in the eastern part, there are more drying trends, although, these are of low significance. We also find some relationships between climate extremes in the Arab region and certain prominent modes of variability, in particular El Niño‐Southern Oscillation ( ENSO ) and North Atlantic Oscillation ( NAO ). The relationships of the climate extremes with NAO are stronger, in general, than those with ENSO , and are particularly strong in the western part of the Arab region (closer to the Atlantic Ocean). The relationships with ENSO are found to be more significant towards the eastern part of the area of study. © 2013 Royal Meteorological Society

Molecular Characterization of Chenopodium album Chloroplast Small Heat Shock Protein and Its Expression in Response to Different Abiotic Stresses - Noor Ul Haq; Muhammad Ammar; Asghari Bano; Dawn S. Luthe; Scott A. Heckathorn; Samina N. Shakeel (Plant Molecular Biology Reporter, 2013)

Lepiota vellingana sp. nov. (Basidiomycota, Agaricales) a new species from Lahore, Pakistan - Rizwana Nawaz; A. N. Khalid; Muhammad Hanif; A. Razaq (Mycological Progress, 2013)

Tephrochronology of the Toba tuffs: four primary glass populations define the 75‐ka Youngest Toba Tuff, northern Sumatra, Indonesia - J. A. WESTGATE; N. J. G. PEARCE; W. T. PERKINS; S. J. PREECE; C. A. CHESNER; R. F. MUHAMMAD (Journal of Quaternary Science, 2013)
Four primary glass populations, well defined by their Sr, Ba and Y concentrations, occur in the Youngest Toba Tuff (YTT), which was deposited during a supereruption of the Toba caldera complex in northern Sumatra 75 ka. Average concentrations of major and trace elements indicate a coherent, systematic variation of glass composition across populations. No clear pattern in the areal distribution of these four glass groups can be discerned. The multiple glass populations of the YTT easily distinguish it from the single homogeneous glass population of the Middle Toba Tuff (∼500 ka), as represented by its basal vitrophyre, and that of the Oldest Toba Tuff (∼800 ka), as represented by ash Layer D at the Ocean Drilling Program site 758 in the Indian Ocean.

Application and Opportunities of Pulses in Food System: A Review - Muhammad Asif; Lloyd W. Rooney; Rashida Ali; Mian N. Riaz (Critical Reviews in Food Science and Nutrition, 2013)

A Multi-Mineral Natural Product Inhibits Liver Tumor Formation in C57BL/6 Mice - Muhammad N. Aslam; Ingrid Bergin; Madhav Naik; Anna Hampton; Ron Allen; Steven L. Kunkel; Howard Rush; James Varani (Biological Trace Element Research, 2012)

A cysteine-rich antimicrobial peptide from Pinus monticola (PmAMP1) confers resistance to multiple fungal pathogens in canola (Brassica napus) - Shiv S. Verma; William R. Yajima; Muhammad H. Rahman; Saleh Shah; Jun-Jun Liu; Abul K. M. Ekramoddoullah; Nat N. V. Kav (Plant Molecular Biology, 2012)

Stimulation of Fibroblast Proliferation by Insoluble Gadolinium Salts - Katherine Bleavins; Patricia Perone; Madhav Naik; Muneeb Rehman; Muhammad N. Aslam; Michael K. Dame; Sasha Meshinchi; Narasimharao Bhagavathula; James Varani (Biological Trace Element Research, 2012)

Comparative adherence to oxybutynin or tolterodine among older patients - Tara Gomes; David N. Juurlink; Muhammad M. Mamdani (European Journal of Clinical Pharmacology, 2012)

Attraction Modulated by Spacing of Pheromone Components and Anti-attractants in a Bark Beetle and a Moth - Martin N. Andersson; Muhammad Binyameen; Medhat M. Sadek; Fredrik Schlyter (Journal of Chemical Ecology, 2011)

Optimisation and characterisation of various extraction conditions of phenolic compounds and antioxidant activity in olive seeds - Muhammad H. Alu’datt; Inteaz Alli; Khalil Ereifej; Mohammad N. Alhamad; Ahmad Alsaad; Taha Rababeh (Natural Product Research, 2011)

Ciprofloxacin-induced theophylline toxicity: a population-based study - Tony Antoniou; Tara Gomes; Muhammad M. Mamdani; David N. Juurlink (European Journal of Clinical Pharmacology, 2011)

Cloning and expression of β-glucosidase gene from Bacillus licheniformis into E. coli BL 21 (DE3) - Sana Zahoor; Muhammad M. Javed; Muhammad N. Aftab; Ikram-ul-Haq (Biologia, 2011)

Determination of Boron Contents in Water Samples Collected from the Neelum valley, Azad Kashmir, Pakistan - Muhammad Akram; Matiullah; Arshid Iqbal; S. N. Husaini; Fariha Malik (Biological Trace Element Research, 2011)

Functional characterization of four APETALA2-family genes (RAP2.6, RAP2.6L, DREB19 and DREB26) in Arabidopsis - Sowmya Krishnaswamy; Shiv Verma; Muhammad H. Rahman; Nat N. V. Kav (Plant Molecular Biology, 2011)

Aflatoxin B1 in chilies from the Punjab region, Pakistan - Shahzad Z. Iqbal; R. Russell M. Paterson; Ijaz A. Bhatti; Muhammad R. Asi; Munir A. Sheikh; Haq N. Bhatti (Mycotoxin Research, 2010)

A Possible Proteome-level Explanation for Differences in Virulence of Two Isolates of a Fungal Pathogen Alternaria brassicae - Nidhi Sharma; Muhammad H. Rahman; Nat N. V. Kav (Journal of Plant Biochemistry and Biotechnology, 2010)

Characterization of Defense Signaling Pathways of Brassica napus and Brassica carinata in Response to Sclerotinia sclerotiorum Challenge - Bo Yang; Muhammad H. Rahman; Yue Liang; Saleh Shah; Nat N. V. Kav (Plant Molecular Biology Reporter, 2010)

Phylogenetic analysis of Bemisia tabaci (Hemiptera: Aleyrodidae) populations from cotton plants in Pakistan, China, and Egypt - Muhammad Z. Ahmed; Shun-Xiang Ren; Nasser S. Mandour; M. N. Maruthi; Muhammad Naveed; Bao-Li Qiu (Journal of Pest Science, 2010)

Enhancing the performance of transplanted coarse rice by seed priming - Muhammad Farooq; Shahzad M. A. Basra; N. Ahmad; G. Murtaza (Paddy and Water Environment, 2009)

Stability of Vitamins during Extrusion - Mian N. Riaz; Muhammad Asif; Rashida Ali (Critical Reviews in Food Science and Nutrition, 2009)

Pancreatic cancer: from molecular pathogenesis to targeted therapy - Alexios Strimpakos; Muhammad W. Saif; Kostas N. Syrigos (Cancer and Metastasis Reviews, 2008)

Targeted therapy for oesophageal cancer: an overview - K. N. Syrigos; A. Zalonis; E. Kotteas; Muhammad Wasif Saif (Cancer and Metastasis Reviews, 2008)

Decolorization potential of mixed microbial consortia for reactive and disperse textile dyestuffs - Muhammad Asgher; H. N. Bhatti; S. A. H. Shah; M. Javaid Asad; R. L. Legge (Biodegradation, 2007)

A Crucial Role for Cytokinins in Pea ABR17-mediated Enhanced Germination and Early Seedling Growth of Arabidopsis thaliana under Saline and Low-temperature Stresses - Sanjeeva Srivastava; R. J. Neil Emery; Muhammad H. Rahman; Nat N. V. Kav (Journal of Plant Growth Regulation, 2007)

Antiproliferative potential of sarcophine and its semisynthetic sulfur-containing derivatives against human mammary carcinoma cell lines - Jamal M. Arif; Swapnali S. Sawant; Khalid A. El Sayed; Muhammad Kunhi; Manogaran P. Subramanian; Yunus M. Siddiqui; Diaa T. A. Youssef; Khalid Al-Hussain; Mohammed N. Al-Ahdal; Fahad Al-Khodairy (Journal of Natural Medicines, 2007)

Autosomal recessive nonsyndromic deafness locus DFNB63 at chromosome 11q13.2–q13.3 - Shahid Y. Khan; Saima Riazuddin; Muhammad Tariq; Saima Anwar; Muhammad I. Shabbir; S. Amer Riazuddin; Shaheen N. Khan; Tayyab Husnain; Zubair M. Ahmed; Thomas B. Friedman; Sheikh Riazuddin (Human Genetics, 2007)

Sex hormone-binding globulin, serum testosterone, and androgen receptors in the skin in papulopustular and conglobata forms of acne vulgaris - N. E. Kushlinskii; I. V. Salamova; S. A. Masyukova; A. Kh. Muhammad; V. G. Degtyar’; V. A. Samsonov (Bulletin of Experimental Biology and Medicine, 1997)